GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 641900100 species occurrences available in GBIF matching the query: All data. The dataset includes 641900100 records from 13328 constituent datasets: 1 records from Cepheus ovalis. 8880 records from Heteroptera. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-065. 23 records from Meiofauna abundance in sediment core 13077-021. 42 records from Planktic foraminifera counts of sediment core ELT48.022-PC. 104 records from Schulwald Sprendlingen. 7344 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 1000 records from Axel W. Erikssons African Birdcollection at Vänersborg Museum. 255559 records from Northern Ireland Environment Agency - EHS Species Datasets. 4591 records from Biological Records Centre - Ticks (Ixodidea) distribution for the British Isles. 48243 records from Biological Records Centre - Millipede (Diplopoda) records for Britain and Ireland to 2005. 2644 records from Planktic foraminifera distribution of sediment core GIK17666-2. 2 records from Nannofossil abundance of Hole 3-18. 502373 records from Hoverfly Recording Scheme - Hoverfly Recording Scheme database for Great Britain. 318 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 92 records from (UTC-MO) University of Tennessee - Molluscs Collection. 60 records from Total foraminifera counts of multinet FCA97C_MSN1344. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 219 records from Umgebung der Grundschule Oderberg. 1599 records from Planktic foraminifera assemblage of sediment core ELT45.029-PC. 918 records from Invertebrate survey, Heard Island 2001. 210 records from Lebensraum Gesamtschule (Langerwehe). 71 records from Planktic foraminifera abundance of Hole 15-153. 1355 records from Planktic foraminifera abundance of Hole 18-173. 136 records from (Table 7) Ostracod assemblages of sediment core 9408. 3362 records from Coimbra Collection of Algae. 47 records from Occurrence of mammalia relicts at site l´Abri de Rhodes II. 23 records from Occurrence of mammalia relicts at site Oblazowa 2. 32 records from Occurrence of mammalia relicts at site Pecurski Karnen. 288 records from Range table from planktonic foraminifers in ODP Hole 154-929E. 523 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ardeidae. 76 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1390. 47 records from Coccoliths in sediment core GIK23059-2. 18 records from Nannofossil abundance of Hole 58-442A. 120 records from Phytoplankton abundance in surface water in June 1997, Chimbote, Peru. 1582 records from Highland Biological Recording Group - HBRG Badger dataset. 487417 records from Instituto de Ciencias Naturales. 4 records from Seodaemun Museum of Natural History Fossil. 47 records from Nannofossil abundance of Hole 94-606. 531 records from Planktic foraminifera counts of sediment core V16-205. 8103 records from Marine Invertebrata specimens deposited in the Fukui City Natural History MUSEUM, Japan.. 24 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 2 records from Nannofossil abundance of Hole 9-79A. 10607 records from Desmidiaceae Engels. 303 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-20. 2 records from Abundance of benthos infauna at station PO128/2_281. 105 records from Countryside Council for Wales - Dormouse Licence Return Data. 7 records from Abundance of radiolaria at station UT99-22-1. 16479 records from MfN - Fossil plants (Cenophytic). 9 records from Nannofossil abundance of Hole 26-255. 3 records from Occurrence of mammalia relicts at site Endingen. 682 records from Range table from planktonic foraminifers in ODP Hole 155-933A. 1 records from Carabodes coriaceus. 55032 records from Collection Arachnology SMF. 222 records from Total foraminifera counts from multinet M31/3_MSN910. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-28-3. 2 records from Abundance of benthos infauna at station GIK23043-2. 324 records from Tentaculata collection of National Museum of Nature and Science. 88 records from Total foraminifera counts of multinet SO118_MSN1265. 45 records from Plasm bearing foraminifera counts from multinet SO119_MSN1286. 228 records from Total foraminifera counts of multinet M36/6_MSN1193. 26 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 337 records from Abundance of calcareous dinocyst along profile Calais-Escalles. 9 records from Microzooplankton abundance and biomass at station TT043_9-1. 121 records from Range table from planktonic foraminifers in ODP Hole 167-1011B. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 46 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 12 records from Abundance of radiolaria at station LV28-44-1. 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 49 records from Occurrence of mammalia relicts at site Felsställe. 420 records from Planktic foraminifera abundance of Hole 23-220. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 1092 records from Caracterización y estructura de la ictiofauna de arrecifes rocosos y coralinos en Punta Carrizal, Colima, México para fines de inventario y conservación de la diversidad animal. 85439 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1987) (AfrOBIS). 21348 records from Phytopathogenic Fungi Observed by Hans and Hanna Doppelbaur. 1312 records from GEO-Hauptveranstaltung (Insel Vilm). 35 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 50 records from Planktic foraminifera abundance of Hole 60-457. 61 records from Range table from benthic foraminifers in ODP Hole 139-857B. 325 records from Planktic foraminifera abundance of Hole 9-83. 1607 records from Range table from benthic foraminifers in ODP Hole 162-986D. 1421 records from Weevils of Poland. 2 records from Eine neue Art der Gattung Suctobelba Paoli (Suctobelba vera n. sp.) aus Deutschland (Acarina: Oribatei). 812 records from Planktic foraminifera abundance of Hole 94-607. 5164 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 106 records from Total foraminifera counts of multinet M42/3_MSN1365. 156 records from Range table from planktonic foraminifers in ODP Hole 155-932B. 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-18-5. 6870 records from Histroical benthic dredge samples from the southern baltic and the North Sea (EurOBIS). 5000 records from Lichen Collection of National Museum of Nature and Science. 19628 records from Bryophytes Collection of National Museum of Nature and Science. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 33 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from the Temburong River basin, Brunei Darussalam, Borneo.. 81 records from Distribución del gecko introducido Hemidactylus frenatus (Dumeril y Bribon 1836) (Squamata: Gekkonidae) en Colombia. 23341 records from Fundación Miguel Lillo - Colección Herpetológica. 215 records from Total foraminifera counts from multinet M31/3_MSN921. 115 records from Total foraminifera counts of multinet M33/1_MSN1028. 348 records from Diplopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 69 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1379. 34 records from Diatom assamblage in samples from sediment trap OG3. 42 records from Macrofauna biomass in surface sediment sampled during cruise DI237. 601495 records from Watervogels - Wintering waterbirds in Flanders, Belgium. 14165 records from NYSM Mammals. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 1294 records from Global Butterfly Information System (GloBIS). 133 records from Range table from benthic foraminifers in ODP Hole 181-1122A. 76 records from Plasm bearing foraminifera counts from M35/1_MSN1075. 3 records from A new species of sponge-dwelling Elacatinus (Pisces: Gobiidae) from the western Caribbean.. 6 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 1489 records from Herbarium Rhoenmuseum Fladungen. 135 records from Waldi-Weiher. 180 records from Paul-Gerhardt-Schule Dassel. 89 records from Birdrace-Team_Wangerooge-Friesland. 5 records from Fledermäuse u. nachtaktive Insekten. 73 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1376. 482 records from Kühmark bei Wetzlar. 22 records from Occurrence of mammalia relicts at site Castlepook Cave. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 175 records from Neißetal. 84 records from Occurrence of mammalia relicts at site Sütto_6. 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 68 records from Occurrence of mammalia relicts at site l´Abri du Morin. 186 records from Planktic foraminifera abundance of Hole 26-255. 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 112 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 1236 records from Percentages of planktonic foraminifera species in sediment core V30-40. 1386 records from Red list project inventory, lichens. 92 records from Nottekanal, Klasse 7 - 10. 48 records from Benthic foraminifera abundance of Hole 42-380A. 210 records from RSPB - Black grouse lek survey in the Scottish Borders, 2010 (Southern Upland Partnership). 93 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 211883652 records from EOD - eBird Observation Dataset. 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 79 records from Total foraminifera counts from M35/1_MSN1055. 3127 records from EcoRecord - Hymenoptera records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 2407 records from Range table from planktonic foraminifers in ODP Hole 139-857A. 22 records from Nannofossil abundance of Hole 26-250A. 8 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_842-3. 290 records from The symphytognathoid spiders of the Gaoligongshan, Yunnan, China (Araneae: Araneoidea): Systematics and diversity of micro-orbweavers. 87143 records from Sheffield Bird Study Group - Sheffield Bird Study Group (Yorkshire records). 111802 records from Highland Biological Recording Group - HBRG Insects Dataset. 41 records from Macrofauna biomass in surface sediment sampled during cruise DI222/2. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 4 records from Zwischen Enz und Schule. 12337 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 19 records from Bayerische Donau - Großmehring. 2 records from Nannofossil abundance of Hole 10-87. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 92 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 32561 records from BIOLOGICAL SCIENCES DATA. 15975 records from condoncollection. 55345 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-9. 7 records from Microplankton counts and carbon biomass at station TT012_5-CTD85. 19 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-139BX. 3 records from Sarcodine counts and carbon biomass at station TT007_12-CTD145. 7 records from Phytoplankton abundance at station Rigel_4_2005-07 in July 2005, Chipana, Chile. 81 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE272. 1559 records from Plathelminthes - SMF. 26753 records from Fish collection of the Museum of Nature and Human Activities, Hyogo. 7 records from Collection Malakologie - SMNG. 145 records from Microplankton abundance in the euphotic zone of the Levantine Sea in October-November 1991. 23 records from Benthic foraminifera abundance of Hole 93-603. 3 records from Dinoflagellate abundance of Hole 85-572. 96 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 3096 records from Biological Records Centre - Mosquito Recording Scheme. 45467 records from UFP - Herbário UFP - Geraldo Mariz. 2577 records from Shellfish (WSHN-MS). 5922 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 131 records from Range table from benthic foraminifers in ODP Hole 189-1172A. 29877 records from Canadian Museum of Nature - Fish Collection (OBIS Canada). 198 records from Phytoplankton abundance in surface water in January 1996, Pisco, Peru. 6987 records from National Trust - Ickworth species data held by The National Trust.. 149 records from Planktic foraminifera abundance of Hole 29-282. 17400 records from Sam Mitchel Herbarium of Fungi (Denver Botanic Gardens). 379 records from Planktic foraminifera assemblage in sediment core GIK17051-3. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-17-7. 22 records from Synonymy of Homalopoltys (Araneae: Araneidae) with the genus Dolichognatha (Araneae: Tetragnathidae) and descriptions of two new species. 3440 records from Actualización de la base de datos del proyecto H278 Apoidea (Hymenoptera) del Valle de Zapotitlán de las Salinas, Puebla. 2940 records from The Erysiphales Collection at the University Halle-Wittenberg. 6723 records from NOAA HML Tidal Creek Database. 590 records from Planktic foraminifera assemblage in sediment core SU90-I08. 884 records from Percentages of planktonic foraminifera species in sediment core EN066-10PG. 17 records from A review of the genus Pareuchiloglanis (Sisoridae) from the Lancangjiang (upper Mekong River) with descriptions of two new species from Yunnan, China.. 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 58 records from Total foraminifera counts of multinet M27/2_MSN882. 783 records from Phytoplankton abundance in surface water during cruise CD61. 500 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 1656 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 116 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 120-748. 144 records from BIRDRACE Punkbirder Helgoland. 2 records from Nothrus palustris. 3978 records from Colección de Entomopatógenos de México (CNRCB). 3653 records from A Dataset of Deep-Sea Fishes Surveyed by Research Vessels in the Waters around Taiwan. 36 records from Occurrence of mammalia relicts at site Trebacki krs. 24 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171C. 21261 records from Sukkulentensammlung Zürich. 2199 records from Plantlife International - Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 96 records from Guadeloupe_manguier. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 34 records from Chaetognatha collection of National Museum of Nature and Science. 25 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_8-CTD93. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 14 records from Phytoplankton abundance at station Sechin_2003-09-18_1, Casma, Peru. 13 records from Range table from benthic foraminifers in ODP Hole 177-1088B. 142 records from Planktic foraminifera abundance of Hole 9-80. 150 records from Phytoplankton abundance in surface water in October 1996, Pisco, Peru. 5056 records from Nest census, Windmill Islands 2002/03. 1 records from Collection Mammalia fossil SMF. 300 records from A systematic revision of the genus Archocentrus (Perciformes: Cichlidae), with the description of two new genera and six new species.. 24 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2446-2. 76124 records from Lichen field notes, Oslo (O). 45 records from Nannofossil abundance of Hole 28-265. 21 records from Meiofauna abundance in sediment core 13077-006. 63 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 42 records from Was singt im Duvenstedter Brook. Wir zählen die Brutvögel im Naturschutzgebiet. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 100504 records from Mammal specimens. 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 1042 records from Planktic foraminifera abundance of Hole 37-333. 237 records from Planktic foraminifera abundance of Hole 21-207. 290 records from Foraminifera abundance of Hole 64-477. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 1020 records from Irish Marine Turtle Database. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 50 records from Range table from benthic foraminifers in ODP Hole 174-1071F. 136 records from Range table from benthic foraminifers in ODP Hole 192-1184A. 1077 records from Percentages of planktonic foraminifera species in sediment core RC24-7. 412 records from Benthic foraminifera counts of sediment core GIK23063-3. 108 records from Planktic foraminifera abundance of Hole 27-263. 59948 records from Polish gene bank – passport data of plants accessions which are important in human life. 1360 records from Collection Tunicata SMF. 427 records from Planktic foraminifera abundance of Hole 76-533A. 269 records from Distribution of planktic foraminifera of sediment trap NB6. 161 records from Total foraminifera counts from multinet SO119_MSN1286. 44 records from Total foraminifera counts of multinet FCA97C_MSN1340. 107 records from Total foraminifera counts of multinet M26/1_MSN844. 95 records from Nannofossil abundance of Hole 15-149. 794 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 1 records from Abundance of benthos infauna at station GIK23040-1. 2500 records from Zooplankton (NSMK-ZP). 2 records from Arthropoden aus südostalpinen Höhlen.. 9605 records from Aves Tanzanian collection at the Natural History Museum of Denmark (SNM). 24972 records from Colección de Herbario. 18 records from Meiofauna abundance in sediment core 13200-012. 577 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 6228 records from Planktic foraminiferal assemblage for the 10kyr time slice from different sediment cores. 127 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 139641 records from Countryside Council for Wales - Marine data from Countryside Council for Wales (CCW) Technical Support (Research & Monitoring) Contracts, Wales. 281 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 523 records from Percentages of planktonic foraminifera species in sediment core V30-49. 2278 records from Benthic foraminifera abundance of Hole 84-568. 90 records from Range table from benthic foraminifers in ODP Hole 146-889B. 33 records from Microfossil abundance of Hole 29-278. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD10. 20 records from Occurrence of mammalia relicts at site Stellmoor. 7 records from Microplankton counts and carbon biomass at station TT008_5-CTD5. 114 records from RSPB - Tree sparrow recovery project â summary data, North West England, 2004-2010 (RSPB, NE, Wirral Borough Council, Cumbria Biodiversity Partnership). 281 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 101 records from Hoher Stein Kallenhardt. 6 records from Boimstorfer Sundern. 26 records from Plasm bearing foraminifera counts from M35/1_MSN1052. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 29 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Baerbel Bleher. 1036 records from Benthic foraminifera distribution of sediment core ASV1200. 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 194 records from Bodenteicher Seewiesen. 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 254 records from BIRDRACE Thüringer Becken-Birders. 1080 records from Distribution of major planktic foraminifer at Site 177-1088. 615 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part I. 166 records from Foraminifera abundance of Hole 22-213. 10000 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 95 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 13 records from Description of lithologic section units of IODP Hole 325-M0031A. 501 records from Planktic foraminifera assemblage in sediment core SU90-I03. 190 records from Foraminifera abundance of sediment core MD81-LC07. 18 records from Planktic foraminifera abundance of Hole 32-310. 404 records from Planktic foraminifera abundance of Hole 94-609B. 759 records from Planktic foraminifera abundance of Hole 47-398D. 248 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 70 records from Planktic foraminifera abundance of Hole 84-569A. 6 records from Sächsische Schweiz (Pfaffenstein). 1 records from Abundance of benthos infauna at station GIK23004-3. 3 records from A new species of Lygistorrhina Skuse (Diptera: Sciaroidea: Lygistorrhinidae) from South Africa. 50834 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 13 records from Tag der Artenvielfalt am Bruckenwasen. 4568 records from Base de datos de las regiones prioritarias 113 y 120 en los municipios de Zirándaro y Coahuayutla, (Guerrero). 60445 records from Bureau of Rural Sciences National commercial fisheries half-degree data set 2000-2002 (OBIS Australia). 634258 records from Hawk Migration Association of North America - HawkCount. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD11. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-12-1. 134 records from National Feral Ferret (Mustela putoris furo) Database. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 3 records from Nannofossil abundance of Hole 51-417D. 68 records from Macrofauna abundance in surface sediment sampled during cruise DI229. 156 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 59 records from Biological Records Centre - RISC Non-Native Species Records for Muntjac. 1251 records from Visual Plants (144.41.33.158) - Herbarium specimen from "EA", Kenya. 267 records from Die Milbenfauna der Nordseeinsel Wangerooge. 31936 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 1 records from Range table from planktonic foraminifers in ODP Hole 175-1081A. 28 records from Occurrence of mammalia relicts at site Bedburg-Königshoven. 11 records from A new species of Probolomyrmex from Madagascar.. 64 records from VFD-RP, Taunus: Bergweide Dehe. 361 records from Stable isotopes and content of foraminifera at Hole 130-805C. 16 records from Occurrence of mammalia relicts at site Nazeing. 536 records from Planktic foraminifera abundance of Hole 14-141. 22 records from Planktic foraminifera abundance of Hole 51-417. 258 records from Planktic foraminifera abundance of Hole 67-500. 4311 records from HVAT - Herbário do Vale do Taquari. 17715 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 19 records from Glemstal (Leonberg). 120 records from Plasm bearing foraminifera counts from M35/1_MSN1060. 265 records from Planktic foraminifera abundance of Hole 73-521. 137 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-35-5. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-06-4. 22 records from Nannofossil abundance of Hole 8-73. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-19-2. 10 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 5 records from Tuttlinger Tag der Artenvielfalt. 55664 records from Fish Specimens. 11 records from Nannofossil abundance of Hole 6-56B. 14 records from Nannofossil abundance of Hole 85-573. 39033 records from SBMNH Vertebrate Zoology. 28 records from Nannofossil abundance of Hole 26-253. 182 records from Range table from benthic foraminifers in ODP Hole 182-1128B. 285 records from Sylva Foundation - European Pear Rust (Gymnosporangium sabinae) monitoring. 39 records from Colección de Urocordados. 36657 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 13 records from Meiobenthos investigations in the Black Sea during Poseidon cruise PO317/3. 40 records from Nannofossil abundance of Hole 47-398. 221 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 9 records from Nannofossil abundance of Hole 11-99A. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/553-3. 855 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V30-97. 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-MNB6. 7443 records from Free-living marine Nematodes from San Antonio bay (Río Negro, Argentine) 2009.. 9 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-913B. 6 records from Oberservation of birds at station PS14/146 along 49° West. 73645 records from Herbario Amazónico Colombiano. 71 records from (Table 3d) Distribution of planktonic foraminiferal tests in sediments from Core NKA-4T. 15 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida), II. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 11 records from Etmopterus burgessi sp. nov., a new species of lanternshark (Squaliformes: Etmopteridae) from Taiwan.. 3734 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 1 records from Arthropoden aus südostalpinen Höhlen.. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 1447 records from Odonata of the Congo River 2010 expedition. 241 records from BIRDRACE RennVögel Münsterland. 1137 records from Plantas Acuáticas de la Orinoquía Colombiana. 7410 records from Helgeland Museum, Lepidoptera. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 80 records from VFD-RP: Taunus: Ponykoppel Thurner. 130 records from Total foraminifera counts from M35/1_MSN1068. 39 records from New records for Albania based on taxa from the Prespa National Park. 150169 records from UWFC Ichthyology Collection. 1 records from Oribates humeralis. 1391 records from Open Mosaic Habitat Survey Group - Plants recorded during Open Mosaic Habitat survey in England and Wales (2012). 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-051. 585 records from Foraminifera abundance of sediment core MD81-LC03. 48 records from Schulgelände (Wetter). 15 records from Occurrence of mammalia relicts at site Barrington. 709 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 24193 records from Joint Nature Conservation Committee - Seabird 2000. 466 records from Akita Prefectural Museum＋Actinopterygius Specimens of Akita Prefectural Museum. 2 records from Luzonichthys seaver, a new species of Anthiinae (Perciformes, Serranidae) from Pohnpei, Micronesia. 197469 records from UMMZ Herpetology Collection. 303 records from National Botanic Garden Belgium - Martius. 3147 records from Range table from planktonic foraminifers in ODP Hole 159-959B. 10 records from Occurrence of mammalia relicts at site Willments Pit. 525 records from Range table from planktonic foraminifers in ODP Hole 155-941A. 38 records from Range table from benthic foraminifers in ODP Hole 139-856B. 22 records from Dinoflagellate abundance of Hole 14-144. 721 records from Tag der Artenvielfalt im Taubental. 1458 records from Waarneming.nl (NL) - Great Grey Shrike Count 2013-2014. 1752 records from Herbier National de Mauritanie (HNM). 69 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 107 records from vegoek. 54 records from Park Schönfeld (Kassel). 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 94 records from Total foraminifera counts of multinet PO231/3_MSN1333. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 21 records from Vogelwelt im Europa-Rosarium. 3394 records from Insect (SMNH-IN). 24 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 3 records from Sarcodine counts and carbon biomass at station TT007_9-CTD108. 38 records from Pollen profile ADR353. 363 records from Planktic foraminifera assemblage in sediment core GIK17730-4. 148 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 10 records from Two new species of eelpouts (Teleostei, Zoarcidae) of the genus Seleniolycus from the Ross Dependency, Antarctica.. 5588 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 446 records from Bayerische Donau - Blindheim Donaubrücke. 591 records from Planktic foraminifera counts of sediment core V23-100. 12681 records from Colección Nacional de Paleobotánica - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 4 records from Estimated plankton abundance at station PS63/064-6. 8649 records from Fossil (WSHN-FO). 343 records from Collection Cnidaria - ZMB. 11893 records from The Lichen Collection at the Botanische Staatssammlung München. 20549 records from Herbier Louis-Marie (QFA) - Collection de lichens. 182 records from Planktic foraminifera abundance of Hole 21-203. 432 records from Planktic foraminifera abundance of Hole 94-606A. 1215 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 6 records from Observation of birds at station PS14/152 along 49° West. 628 records from hauterivian_echinoids_of_the_paris_basin. 264 records from Range table from benthic foraminifers in ODP Hole 146-892A. 192 records from "Schwarzwassertal" bei Pobershau. 7 records from Pollen and spore abundance of Hole 42-380A. 301 records from Gyeryonsan Natural History Museum Bird . 16118 records from Database of Fungal Specimens Maintained at the Selected Japanese Herbaria. 5126 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 8124 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 85 records from Total foraminifera counts from M35/1_MSN1065. 13503 records from Collection of various insect orders, Natural History Museum, University of Oslo. 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 15 records from Regenwasserabfangsbecken (Erlenbach). 97 records from Landschaftspark St.Leonhard-Deisendorf. 279 records from BIRDRACE Wannacks Topti(c)ker. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 70 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1387. 48 records from Diatom assamblage in samples from sediment trap OG5. 3437 records from Opiliones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 42788 records from Merseyside BioBank - North Merseyside Insects (unverified). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 204 records from Range table from benthic foraminifers in ODP Hole 171-1051A. 1 records from Results of palynological analysis of Hole 302-M0001A. 42920 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 47 records from Schulgelände Grolland. 138 records from Phytoplankton abundance at station DI182_11863#1. 7 records from Nannofossil abundance of Hole 7-64. 104 records from Planktic foraminifera abundance of Hole 63-473. 18 records from Range table from planktonic foraminifers in ODP Hole 182-1128A. 2 records from Microzooplankton abundance and biomass at station TT050_11-4. 7 records from Microplankton counts and carbon biomass at station TT008_5-CTD18. 24 records from Range table from benthic foraminifers in ODP Hole 192-1185B. 87 records from Benthic macrofauna abundance and biomass in surface sediment during cruise PLG93. 47672 records from Birds (KIDR-BI). 73 records from Faunal assemblage of sediment core GS7603-13. 2088 records from Benthic foraminifera of sediment core MD99-2286. 41460 records from Herbarium (UNA). 99 records from Occurrence of mammalia relicts at site l´Abri de Combe-Cullier. 67 records from Plasm bearing foraminifera counts from M35/1_MSN1054. 57 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1195. 90 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1378. 79 records from Sedimentological investigation on core V25-60. 14 records from Occurrence of mammalia relicts at site Petnicka Pecina. 11 records from Range table from planktonic foraminifers in ODP Hole 178-1096C. 5 records from Occurrence of mammalia relicts at site Grotte de la Martine. 3 records from Range table from planktonic foraminifers in ODP Hole 183-1141A. 8 records from Pollen and spore abundance of Hole 42-380. 300 records from Gunma Museum of Natural History, Fish Specimen. 2 records from A new species of Neossos Malloch (Diptera: Heleomyzidae) from the Yukon Territory, Canada, and a revised key to the Nearctic species. 94 records from Total foraminifera counts from M35/1_MSN1074. 1322 records from Planktic foraminifera abundance of Hole 29-284. 88 records from Total foraminifera counts of multinet PO247/2_MSN1384. 589 records from National census of Lepidochelys olivacea (Benin). 15 records from Microfossil abundance of Hole 39-358. 420 records from Dinocyst occurrences and zonations from IODP Hole 313-M0027A. 5 records from Calculated abundance and biomass of Ophiocten gracilis at different stations on Kolbeinsey Ridge. 11 records from Microplankton abundance at bottle station SEPT-1999-K3. 15 records from Occurrence of mammalia relicts at site Brühl 1. 151 records from Planktic foraminifera abundance of Hole 11-104. 199 records from La fauna de Melolonthidae, Cerambycidae y Elateridae (Insecta: Coleoptera) de la reserva de la biósfera El Triunfo, Chiapas. 26143 records from Partial Amphibians Collection. 541 records from Planktic foraminifera abundance of Hole 33-315A. 8469 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 20 records from Occurrence of mammalia relicts at site Kesslerloch. 496 records from Range table from benthic foraminifers in ODP Hole 145-887A. 68 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/587-14. 11 records from Microzooplankton abundance and biomass at station TT045_15-2. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 2 records from Dinoflagellate abundance of Hole 85-572C. 10792 records from Fungi specimen detabase of Kanagawa Prefectural Museum of Natural History. 235 records from Range table from benthic foraminifers in ODP Hole 161-974B. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 1 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 22 records from Dellwiger Bach (Dortmund). 49 records from Dörnberg. 82 records from BIRDRACE Die Ziegeneier. 2421 records from Census of plant species in Toffo forest reserve. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 1770 records from Schmidt Museum of Natural History_Birds. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1049. 22 records from Phytoplankton abundance at bottle station GOM6/1. 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE275. 9 records from Microzooplankton abundance and biomass at station NBP97-03-05-6. 135 records from Range table from planktonic foraminifers in ODP Hole 171-1050A. 631 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 149-898A. 107982 records from Botany Division, Yale Peabody Museum. 1264 records from Hare Survey of Ireland 06/07 - Non Hare records. 19 records from Pollen profile from Achenhang. 2374 records from DSMZ Collection of Filamentous Fungi and Yeasts. 39035 records from Merseyside BioBank - North Merseyside Birds (unverified). 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 39 records from Stausee Weiditz. 5 records from Sarcodine counts and carbon biomass at station TT012_3-CTD5. 1465 records from Centro Nacional Patagonico Ichthyological Collection (OBIS South America, SOUTHERN OCEAN SUB-NODE). 47502 records from Fish specimen database of Osaka Museum of Natural History. 9625 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 303 records from Planktic foraminifera abundance of Hole 94-608A. 21 records from Range table from planktonic foraminifers in ODP Hole 139-855B. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 15 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0003A. 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 16425 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 29 records from Klimaoasen in Köln. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 83 records from Planktic foraminifera abundance of Hole 14-135. 163 records from Planktic foraminifera abundance of Hole 32-313. 161 records from A conspectus of the native and naturalized species of Nephrolepis (Nephrolepidaceae) in the world. 23 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 11 records from Collection Xiphosura SMF. 6 records from Content of coarse fraction and G. menardii in sediment corev V25-64. 10 records from Content of different diatom species in sediment core GIK23259-2. 19955 records from ELM paleontology. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_1-CTD1. 734 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Icteridae. 1471 records from EcoRecord - Bryophyte records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 164 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 1 records from Zetes ephippiatus. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 72 records from Faunal assemblage of sediment core TR149-35. 2233 records from Chrysomelidae of Poland. 105 records from Plasm bearing foraminifera counts of multinet M21/5_MSN731. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-015. 16 records from Benthic macrofauna abundance of sediment core 13200-045. 3855 records from Icota - Pelagant. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 56 records from Nannofossil abundance of Hole 94-607. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-087. 103 records from Pollen analysis of Site 175-1075 (part 1). 37 records from Range table from planktonic foraminifers in ODP Hole 172-1060A. 73 records from Phytoplankton abundance in surface water in January 1996, Chimbote, Peru. 10699 records from Biological Records Centre - Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 192839 records from Entomology Division, Yale Peabody Museum. 212520 records from Limnodata. 54 records from Total foraminifera counts from M35/1_MSN1057. 55 records from Microzooplankton abundance measured on water bottle samples at station PS65/466-2. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 48 records from Trockenrasen bei Dörndorf. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 84 records from BIRDRACE Birding for Nature. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 82 records from Plasm bearing foraminifera counts from M35/1_MSN1050. 34 records from Total foraminifera counts of multinet M21/4_MSN717. 234 records from Clyde River Foundation - Allis Shad (Alosa alosa) distribution for Scotland, historical to present. 16 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 186 records from Total foraminifera counts of multinet M21/1_MSN604. 23 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5136-1. 3 records from Collection Aves fossil SMF. 49 records from Museu Paraense Emilio Goeldi - Uropygi Collection. 20755 records from pins. 8518 records from Upper Silesian Museum, Bird Observations. 1594 records from Musée Vert ornithology collection. 13 records from Nannofossil abundance of Hole 11-103. 355 records from Dinoflagellate abundance of Hole 94-607. 1018 records from Planktic foraminifera abundance of Hole 9-84. 337366 records from British Lichen Society - BLS Lichen Database: England. 7 records from Abundance of nematoda in sediment profile M3/1_029 from the Iberian deep sea basin (Table 5). 32 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2002. 305 records from Flux data of NU2_trap (Table A1). 16 records from Moenkhausia pankilopteryx, new species from rio Tocantins drainage, Brazil (Ostariophysi: Characiformes, Characidae).. 1 records from Hypochthonius rufulus. 80 records from Förderzentrum Schmölln. 113 records from Rund um das LUGY. 1801 records from Alterra (NL) - Entomofauna inventory in dead wood. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 22854 records from National Botanic Garden Belgium - Myxomycetes. 82 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ciconiidae. 33070 records from CSIRO Ichthyology provider for OZCAM. 18 records from Content of coarse fraction and G. menardii in sediment corev V25-57. 1 records from Phytoplankton abundance at station Rigel_3_2005-08 in August 2005, Chipana, Chile. 47 records from Revised diagnosis of the genus Bangana Hamilton, 1822 (Pisces: Cyprinidae), with taxonomic and nomenclatural notes on the Chinese species.. 131 records from Total foraminifera counts from multinet M32/3_MSN956. 154 records from Total foraminifera counts of multinet M36/6_MSN1197. 2 records from Nannofossil abundance of Hole 3-14. 9 records from Nannofossil abundance of Hole 26-250. 213 records from Amphibian and Reptile (JNHM-AR). 573 records from Macrobenthic species of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 566 records from (Appendix A1) Distribution of benthic foraminifera in ODP Site 184-1143. 708 records from Phytoplankton samples - 2005/06 V3 BROKE-West. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 195 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 13195 records from Fish Collection of Natural History Museum and Institute, Chiba. 67661 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1994) (AfrOBIS). 778 records from Planktic foraminifera abundance of Hole 40-362. 318 records from Nematode abundance in cold seep sediments of the Darwin mud volcano. 774 records from Planktic foraminifera abundance of Hole 80-549A. 57 records from Range table from planktonic foraminifers in ODP Hole 152-915A. 506 records from Range table from benthic foraminifers in ODP Hole 146-889A. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 6062 records from Lichens of Knyszyn Forest. 771 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3947 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 1709819 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 66 records from Mammals (KIEE-MM). 5549 records from Diplopoda (NSMK-DI). 85 records from Plasm bearing foraminifera counts from M35/1_MSN1053. 370 records from Collection Crustacea - KAUMM. 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 195 records from Total foraminifera counts from multinet M31/3_MSN923. 1296 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-229. 242 records from (Fig. 3) Age and multiproxy studies of sediment core GeoB7186-3. 494 records from Biologische Station im Kreis Wesel. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 6782 records from Zooplankton Abundance Based on Taxa and Life Stages or Size. 212 records from Am Moosangerweg. 157 records from Bizzenbachtal (Wehrheim/Taunus). 148 records from Hintere Halde. 189 records from Fish larvae biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 468 records from Distribution of planktic foraminifera in surface sediment samples from cruise SO136. 3 records from Benthic foraminifera abundance of Hole 96-621. 42 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Passeridae. 398 records from Tsetse flies of East Africa update. 3091630 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 185 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 1054 records from University Marine Biological Station Millport - 1999-2009 UMBSM Clyde Sea Fairlie Channel Beam Trawl Survey. 34 records from Benthic foraminifera abundance of Hole 42-381. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 98 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 71 records from (Data S1) Palynology of ODP Site 113-696. 21188 records from National Bat Database of Ireland. 1 records from Waldtag in und um Seelingstädt. 2412 records from Ohio University Invertebrate Paleontology Collection. 217 records from Nanoplankton abundance at station GeoB2012-2. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 3 records from Nannofossil abundance of Hole 31-301. 202194 records from Tulane University Museum of Natural History. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 991 records from Foraminifera abundance of Hole 64-481A. 47 records from Planktic foraminifera abundance of Hole 72-515. 323085 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 12111 records from DMNS Marine Invertebrate Collection (Arctos). 761 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Walther Herwig cruise WH220. 13960 records from Collection Trichoptera - SMF. 3021 records from IBB bacterial database. 5445 records from ChEssBase (CoML). 9211 records from Árboles y Arbustos Nativos para la Restauración Ecológica y Reforestación de México (IE-DF,UNAM). 570 records from Planktic foraminifera abundance of Hole 94-606. 219 records from Total foraminifera counts of multinet M21/5_MSN730. 3 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Nyctibiidae. 9 records from Occurrence of mammalia relicts at site Siebenlinden 1. 176 records from Planktic foraminifera abundance of Hole 62-463. 331 records from Size of planktic foraminifera at CTD station PS55/082-1. 65 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211670-7. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 12 records from Abundance of radiolaria at station LV28-40-2. 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 1354 records from Collection Crustacea ZMG. 96 records from Range table from planktonic foraminifers in ODP Hole 182-1126D. 25 records from Benthic foraminifera abundance of Hole 1-4. 164 records from Range table from benthic foraminifers in ODP Hole 192-1186A. 18 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-860B. 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 423 records from Bird Collection of Otto Hedin. 169 records from Whale log - observations from ANARE voyages. 8 records from UWYMV Herpetology Collection (Arctos). 45 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 875 records from Fish monitoring data in Lake Kasumigaura. 101 records from MVZ Mammal Observations (Arctos). 252060 records from Moths Ireland. 10885 records from RSPB - Swift Inventory of Nest Sites in the UK, 2009 (RSPB and Swift Conservation Groups). 2880 records from Coleoptera, NEF. 54 records from Range table from planktonic foraminifers in ODP Hole 173-1067A. 22 records from Phytoplankton abundance in surface water in January 2007, Sechura Bay, Peru. 42 records from Collection Aves - PUM. 16383 records from Scottish Environment Protection Agency - Scottish river macro-invertebrate records from 2007 collected by SEPA. 234 records from Baggerseen bei Krauchenwies. 1200 records from Insect specimens of Natural Museum of Geihoku. 2 records from Nannofossil abundance of Hole 31-300. 1458 records from Hertfordshire Biological Records Centre - Hertfordshire Lowland Meadow Inventory Survey 2010. 73 records from Phytoplankton abundance at several stations in January 2005, Chipana, Chile. 18 records from Phytoplankton abundance at station Rigel_4_2005-04 in April 2005, Chipana, Chile. 10046 records from Marine Biological Association - Marine Life Survey Data (collected by volunteers) collated by MarLIN. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/587-1. 11 records from Benthic macrofauna abundance of sediment core 12930-063. 10060 records from Shellfish (NSMK-MS). 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-17-4. 45 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE258. 1498 records from Marine invertabrate(ARTHROPODA) specimen database of Osaka Museum of Natural History. 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 1868 records from Inventario florístico de la Sierra de San Carlos, Tamps. 2320 records from Planktic foraminifera assemblage of sediment core ELT49.018-PC. 425 records from Moss sampling in the Windmill Islands and the Vestfold Hills. 129 records from Streuobstwiese Kattenhund (Schleswig). 59 records from Planktic foraminifera abundance of Hole 28-266. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 1 records from Microplankton counts and carbon biomass at station TT007_10-CTD123. 394 records from Planktic foraminifera counts of sediment core V29-45. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 501 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 64 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 77 records from Total foraminifera counts from M35/1_MSN1075. 66 records from Foraminifera species abundances from tow TT007_10-MOC20. 611 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Chavez 2011. 1 records from Ulteriore contributo alla conoscenza dei chilopodi di Grecia. 1 records from Arthropoden aus südostalpinen Höhlen.. 28 records from A new species of the freshwater fish genus Astyanax (Ostariophysi: Characidae) from the rio Iguacu basin, southeastern Brazil.. 110 records from Abundance of planktic foraminifera at CTD station M39/4_366CTD-22. 54 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211660-6. 1360 records from Contribución a la riqueza ictiofaunística de la Reserva de Ría Lagartos, Yucatán. 556 records from Distribution of planktic foraminifers of sediment core D117. 385 records from Benthic foraminifera abundance of Hole 76-533. 2 records from Abundance of benthos infauna at station PS1239-1. 127 records from Collection Ephemeroptera - SMF. 3592 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 26 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 1 records from Hoplophora crinita. 55 records from Waldsee. 88 records from Upper Aptian Niveau Kilian range chart of nannofossils in SE France. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/508-2. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-070. 308 records from Planktic foraminifera counts of sediment core V19-178. 35 records from Total foraminifera counts of multinet M42/3_MSN1368. 10 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-22-5. 109504 records from Plant Specimens of Kurashiki Museum of Natural History. 97 records from CNIN/Tipos Hymenoptera. 200 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE233. 162 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano. 1 records from Arthropoden aus südostalpinen Höhlen.. 95 records from Überschwemmungsgebiet der Wied. 3 records from Analyses of the recent components of sediment core PS1215-2. 12 records from Abundance of microplankton from bottle APRIL-2000-K4. 19 records from Occurrence of mammalia relicts at site Gröbern. 68 records from Planktic foraminifera abundance of Hole 22-213. 108 records from Occurrence of mammalia relicts at site l´Abri du Flageolet I. 164 records from Planktic foraminifera abundance of Hole 22-215. 169 records from Relative abundance of planktonic foraminifera in sediment core L-348. 33 records from Range table from planktonic foraminifers in ODP Hole 175-1078B. 340 records from Kiesbagger (Mittelhausen). 3 records from Microfossil abundance of Hole 50-415. 234 records from Artenvielfalt der Nordsee - Sylt. 400 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 268876 records from Fiji Terrestrial Arthropods. 2 records from Abundance of benthos infauna at station GIK23025-2. 662 records from RSPB - Snipe survey of key sites in Britain in 2006 (RSPB and Natural England). 1 records from Zetes latirostris. 9719 records from The Orchid Atlas of Western Australia. 79 records from Benthic foraminiferal assemblage (dead) in MUC OB10-K, size fraction >150 µm. 149 records from Total foraminifera counts of multinet SO117_MSN1243. 138 records from Plasm bearing foraminifera counts from multinet SO119_MSN1278. 76 records from Range table from benthic foraminifers in ODP Hole 139-856A. 117 records from Total foraminifera counts of multinet PO231/3_MSN1329. 1227 records from EcoRecord - Crustacean Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 47 records from Occurrence of mammalia relicts at site Burgtonna. 9 records from Radiolaria assemblage in sediment core GIK23411-5. 93 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cotingidae. 8 records from Pollen analysis of sediment profile BUA1 from Buchsee. 5173 records from Planktic foraminifera abundance of Hole 15-147. 83 records from Foraminifera species abundances from tow TT011_7-MOC66. 18 records from Benthic macrofauna abundance of sediment core 13200-075. 105 records from Planktic foraminifera abundance of Hole 18-181. 330 records from Phytoplankton abundance in surface water in February 1998, Pisco, Peru. 109452 records from Biological Records Centre - Cranefly (Diptera; Tipuloidea) records for Britain to 2007. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 177466 records from CAS Entomology (ENT). 160 records from Plasm bearing foraminifera counts from M35/1_MSN1068. 896 records from Coleção de Ictiologia do Museu de Ciências Naturais do Centro Universitário Univates (ZIUMCN-UNIVATES). 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 44802 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 43645 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 45358 records from 2011 Breeding Bird Survey of Taiwan. 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 3594 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 117 records from Wassermann. 5793 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 54 records from Königsdorfer Wald. 109 records from Benthic foraminifera abundance of Hole 56-436. 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 81 records from Umgebung des Spalatin Gymnasium Altenburg. 61 records from Fürstenberger Ralley Teil 3. 105 records from BIRDRACE coesfelder_vogelkundler. 73 records from VFD-HH/SH: Pferdweide Lammert. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 337 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Falconidae. 1887 records from Threatened Species programme. 15835 records from Amphibians and Reptiles collection at the Natural History Museum of Denmark (SNM). 62428 records from South East Wales Biodiversity Records Centre - Microlepidoptera of Glamorgan. 191 records from Herbarium specimens of Bamboo collection Prafrance Générargue (BAMBO). 1458 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 113482 records from KUBI Ornithology Collection. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 458 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 356 records from Biotope in Rheine - Aktion 350. 177 records from Donauinsel des BN bei Entau. 50 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 1 records from Arthropoden aus südostalpinen Höhlen.. 970 records from Benthic foraminifera and algae abundance of Hole 81-555. 97 records from New distributional data on aquatic and semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha & Nepomorpha) from South America. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 2506 records from Museu Paraense Emilio Goeldi - Opiliones Collection. 314 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 52 records from Sedimentology and stratigraphy of core OD96_41:4:1. 885 records from Asteroids from French subantarctic islands: records from the Marion Dufresne MD03 expeditions. 1 records from Oribates calcaratus. 2494 records from Colección de peces dulceacuícolas de Costa Rica. 17618 records from BioGIS - Mammals - INPA database. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 95 records from BIRDRACE BiBi. 15 records from Pogonophora collection of National Museum of Nature and Science. 13 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (verified). 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 12077 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 51 records from Mühlenbach bei Buxtehude. 20 records from Range table from planktonic foraminifers in ODP Hole 175-1078C. 100 records from National Biodiversity Network Trust - Demonstration dataset for record commenting on the NBN Gateway. 1017 records from Broadland Environmental Services Limited - Water vole distribution within Broadland (2003-2006): based upon field signs, sightings and trapping data.. 300 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part II. 1011 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 64240 records from The Scottish Ornithologists' Club - South East Scotland Tetrad Atlas 1988 - 1994 - non-sensitive breeding species. 60 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Steffen Matezki. 11370 records from Distribution of planktic foraminifers of core V22-174. 3161 records from Distribution of foraminifera of sediment core ENAM93-21. 1101 records from Relative abundance of ostracods in sediment core Co1202. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 1308 records from Dinoflagellate cysts counts of sediment core MD95-2010. 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 1298 records from Planktic foraminifera abundance of Hole 23-219. 11 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_236-1. 31 records from Biological data measured on water bottle sampels at station AT_II-119/5_31-7. 85 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 6659 records from Anfibios y Reptiles del Estado de Tamaulipas, México (UANL). 371 records from Planktic foraminifera abundance of Hole 63-470. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/546-2. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 1000 records from Diplopoda (JJHA-DI). 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 655 records from Planktic foraminifera assemblage in sediment core GIK17049-6. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 64 records from Total foraminifera counts of multinet M42/3_MSN1369. 38 records from Microfossil abundance of Hole 21-206C. 1 records from Dinoflagellate abundance of Hole 19-183. 52 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1382. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 32 records from Microzooplankton abundance measured on water bottle samples at station PS65/593-3. 8276 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 199059 records from KU Museum of Invertebrate Paleontology. 104 records from Total foraminifera counts of multinet M21/6_MSN778. 65535 records from OAC-BIO Herbarium. 57 records from Upper Aptian Serre Chaitieu (Niveau Fallot) G. ferreolensis and G. blowi per gram sediment, SE France. 20 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD88. 3 records from Sarcodine counts and carbon biomass at station TT011_2-CTD21. 349988 records from BSBI tetrad data for Ireland. 244 records from Range table from benthic foraminifers in ODP Hole 145-887C. 62 records from Range table from benthic foraminifers in ODP Hole 151-907A. 24204 records from EKY_Darwincore. 131 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 432 records from Range table from benthic foraminifers in ODP Hole 172-1057B. 116 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (75° N section). 236165 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Red list project inventory, bryophytes. 959 records from RSPB - Black-throated diver national surveys in Scotland (SCARABBS). 21 records from Planktic foraminifera abundance of Hole 1-5. 1012 records from Amphibian and Reptile Conservation - NARRS Data 2007 - 2011. 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-098. 1 records from Arthropoden aus südostalpinen Höhlen.. 23 records from Meiofauna abundance in sediment core 12930-075. 9494 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 2324 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 170 records from Nanoplankton abundance at station GeoB2021-1. 5 records from Nannofossil abundance of Hole 67-499B. 1 records from Nothrus bistriatus. 4021 records from Herbarium Specimen of the Institute of Traditional Medicine, Tanzania. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI229. 1445 records from Shellfish (GNHM-MS). 1906 records from Fossil (MNHM-FO). 44 records from Planktic foraminifera assemblage in sediment core GIK23256-1. 2303 records from Planktic foraminifera abundance in per cent of Hole PRAD1-2. 72 records from Range table from planktonic foraminifers in ODP Hole 172-1058A. 150 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 16344 records from Coleccion de sonidos ambientales. 159 records from VFD-BW, Oberrhein/Schwarzwaldrand: Pferdeweiden Liel. 781 records from Inventario de Aves y Mamíferos en humedales del departamento de Córdoba. 10 records from Nannofossil abundance of Hole 38-338. 4 records from Nannofossil abundance of Hole 85-574. 2355 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 7 records from Abundance of radiolaria at station LV28-7-1. 1343 records from Bryophyte specimens of Iwate Prefectural Museum. 251 records from Benthic foraminifera abundance of Hole 80-549A. 21847 records from CUMV Mammal Collection (Arctos). 1 records from Nothrus bicarinatus. 2960 records from Herp specimens. 73 records from Tiergarten (Zeitz). 1 records from Nothrus sordidus. 2283117 records from Australian Museum provider for OZCAM. 107 records from Müritz-Nationalpark. 1393 records from Lepidoptera from Rancho Grande, Rondônia, Brasil. 11981 records from SMNK Mantid Collection. 102524 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 68081 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1995) (AfrOBIS). 1 records from Nothrus bispinosus. 555 records from FFH-Gebiet "Calwer Heckengäu". 29513 records from MPM Herpetology. 1 records from Nothrus palliatus. 91 records from BIRDRACE NABU LV Hessen. 62 records from Lebensraum Dorf. 80 records from Feldweg Waldkirchen. 2475 records from HSU Wildlife Eggs and Nests. 287 records from BIRDRACE Pody und Co. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 41 records from Nachtaktiv im Ökogarten (Bad Waldsee). 1458 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 2385 records from Collection Messelpaläobotanik SMB. 3784 records from Herbier de Wallis et Futuna. 1 records from Zetes latipes. 2048061 records from Museum of Comparative Zoology, Harvard University. 353326 records from UCJEPS TAPIR Provider. 233 records from Föhrenried (Fronreute und Baindt). 4310 records from MfN - Fossil vertebrates V. 1 records from Der Kreuzenzian und sein Bläuling. 1517 records from IBF Monitoring of Fungi. 396496 records from IBF Monitoring of Vascular Plants. 3045 records from ESAS cetacean sightings from 1980 to 2003.. 2 records from Nannofossil abundance of Hole 66-488. 144 records from BIRDRACE Die Mohrenlerchen. 162 records from Siegen/ Gymnasium Am Löhrtor. 31 records from Siphonaptera. 59 records from Oschenberg, NO von Bayreuth-Laineck. 1117 records from Fossil (NSMK-FO). 7284 records from UFMT - Herbário UFMT. 89 records from Schulgelände Paul-Gerhardt-Schule. 2427 records from Ibaraki Nature Museum, Mollusk collection. 3204 records from Faunal Inventory of Morysin Nature Reserve. 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 18 records from Meiofauna abundance in sediment core 13368-015. 106100 records from Fish (NSMK-PI). 234 records from Phytoplankton samples - 2006/07 V3 SAZ-Sense. 14202 records from Plant specimens of Hokkaido University Museum. 201 records from Mycological collections of the University of Tartu. 13736 records from MfN - Mallophaga Collection. 50 records from Junge Heide, Radebeul/Dresden. 32 records from Schulhof Sandhofenschule (Mannheim). 30 records from Riekdahler Wiesen. 23836 records from Korea Bird Distribution Atlas Database. 13478 records from Herp Collection. 398 records from Mooswald (Freiburg). 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 131 records from BIRDRACE Brut. 975 records from Danielsberg (Mölltal, Kärnten). 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 13 records from FND "Weißer Berg" Leißling. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 126 records from Total foraminifera counts from M35/1_MSN1050. 156 records from Dinoflagellate cysts of mooring MST-9 (station 915) with cell content. 49 records from Pollen profile form Hickory Ridge Basin, Illinois, U.S.A. 209 records from Relative abundance of coccosphere-units at site GIK23414. 16 records from Coccolith counts of multinet M32/5_MSN986. 3 records from Nannofossil abundance of Hole 94-609A. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/046-3. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/090-4. 558 records from (Table 5) Pleistocene ostracodes from ODP Hole 104-644A. 1218 records from (Table 6) Relative abundances of the seven species of planktonic foraminifera from ODP Site 108-662. 1134 records from Ictiofauna de los corredores biológicos Sierra Madre del Sur y Selva Maya Zoque. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 138 records from Total foraminifera counts of multinet M10/2_MSN297. 11 records from Zoobenthos in surface sediments off Cape Lucul. 6 records from Wiese. 451 records from Nannofossil abundance of Hole 15-148. 21 records from Nannofossil abundance of Hole 6-55. 818 records from Range chart of calcareous nannofossils from ODP Hole 188-1165B (Table 1). 131 records from (Table 3) Occurrence of benthic foraminifera in the Ledyanaya section. 3910 records from Plant (MNHM-PL). 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 216 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE236. 1972 records from (Figure 6) Distribution chart of benthic foraminifers in ODP Site 126-792. 1691 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 75655 records from Ibaraki Nature Museum, Vascular Plants collection. 12717 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 274 records from Foraminifera abundance of sediment core BM1958.631. 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 15586 records from Historical quantitative benthos grab samples from the Southern Baltic Sea (EurOBIS). 313949 records from United States National Plant Germplasm System Collection. 117 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A. 13225 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 1505 records from Relative abundance of planktonic foraminifera in Pliocene and Pleistocene sediments of DSDP Hole 32-310 from Hess Rise, Central North Pacific (Table II). 780 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 48 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 1 records from Occurrence of mammalia relicts at site Kleine Feldhofer Grotte. 26 records from Planktic foraminifera abundance of Hole 20-200A. 126 records from Planktic foraminifera abundance of Hole 32-305. 320 records from Range table from planktonic foraminifers in ODP Hole 141-863A. 176 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 240 records from Range table from benthic foraminifers in ODP Hole 175-1075A. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 769 records from Range table from benthic foraminifers in ODP Hole 145-883B. 99159 records from Biological Records Centre - Dragonfly and Damselfly (Odonata) records for Britain to 1992, from the former Dragonfly Recording Scheme. 20 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2004. 1849 records from National Trust - Heigham Holmes species data held by The National Trust. 1207 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 128 records from Total foraminifera counts of multinet M33/1_MSN1030. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-18-1. 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 1825 records from Galathea II, Danish Deep Sea Expedition 1950-52. 5233 records from (Appendix A) Stable carbon and oxygen isotopes and paleoproductivity reconstructions for the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 877 records from Benthic foraminifera distribution of sediment core ASV11-987 (ASV987). 46 records from An der Ohm, (Wettsaasen). 28 records from Occurrence of mammalia relicts at site Climauti II. 3119 records from Hormigas en cultivos de naranja (Citrus sinensis (L.) Osbeck) de la costa Caribe de Colombia. 2259 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 463 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 45 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/009-2. 21795 records from Computarización de la colección de abejas (Hymenoptera: Apoidea) del Museo de Zoología Alfonso L. Herrera, de la Facultad de Ciencias de la UNAM. 921 records from Importancia de las lombrices de tierra (Oligochaeta) en el monitoreo de áreas prioritarias de conservación del centro, este y sureste de México. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 82953 records from Vascular Plants, Observations, Oslo (O). 257 records from Kernberge und Umgebung (Jena). 17 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 2357 records from Foraminifera abundance of Hole 17-167. 525 records from Planktic foraminifera abundance of Hole 94-609. 18039 records from Sponges of Rathlin Island. 70 records from Exotic terrestrial flatworms, Macquarie Island. 1639 records from Avena wild species collection. (N.I.Vavilov Institute of Plant Genetic Resources (VIR)). 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 881 records from Moluscos Marinhos de Augusto Nobre. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 26 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 10 records from Benthic macrofauna abundance of sediment core 13078-017. 8980 records from MEXU/Tipos de plantas vasculares. 80 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 1. 31 records from Description of a new species of Acestridium (Siluriformes: Loricariidae) from Colombia.. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 347088 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 1 records from Miriapodi di alcune grotte della Campania. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 192273 records from Field Museum of Natural History (Zoology) Mammal Collection. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 35 records from Gym Freyung. 3000 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 100 records from (Table 4) Distribution of nannofossils in DSDP Hole 87-583D. 23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1). 1 records from Zetes semirufus. 535 records from Distribution of microorganisms in recent sediments of Kiel Bay. 31082 records from MEXU/Plantas Vasculares. 1351 records from Neogene palynomorpha from site 93-603, part 1. 1 records from Planktic foraminifera abundance of Hole 8-72. 256574 records from R. L. McGregor Herbarium Vascular Plants Collection. 34140 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 12 records from Abundance of epibenthic echinoderms at seafloor photography station M21/5_317. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 403 records from (Appendix A) Relative abundance of Emiliania huxleyi in sediment cores of the North Atlantic. 232018 records from MVZ Mammal Collection (Arctos). 119366 records from The digitization of plant specimens of NTU. 2 records from Amphibia ZMK. 15 records from AKG-Bensheim. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 3860 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 85783 records from Birds (KIEE-BI). 210 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 1161 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 66 records from Foraminifera abundance of Hole 55-432A. 401 records from Range table from planktonic foraminifers in ODP Hole 138-852B. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1095A. 73 records from Fossil (JNHM-FO). 2546 records from Nature Locator - PlantTracker data from 2012 onwards. 280 records from (Figure 1d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3202. 1116766 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 30 records from (Table 2) Benthic isopod species of the Ross Sea, their bathymetry and distribution in the Southern Ocean. 306 records from Camera trap database of Tiger from Rajaji National Park, Uttarakhand. 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 101 records from Birdrace-Herford-Birder-Herford. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 178 records from Total foraminifera counts of multinet M6/7_MSN148. 501 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-075. 10 records from Benthic macrofauna abundance of sediment core 12930-044. 1340 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 241 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 18302 records from Mycology Herbarium, Trondheim (TRH). 37641 records from Nordic Genetic Resources. 3634 records from Herpetological collection of National Museum of Nature and Science. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 1115 records from Distribution of planktic foraminifera (200-630 µm) of sediment core M8_057-2 (Table 4). 53 records from Planktic foraminifera abundance of Hole 29-281A. 899 records from (Fig. 13) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 80-549 in the North Atlantic. 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 89 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (75° N section). 4 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 10121 records from Arachnologie - SMNG. 3664 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 4 records from Tropidomyrmex elianae, a new myrmicine ant genus and species from Brazil, tentatively assigned to Solenopsidini (Hymenoptera, Formicidae).. 16648 records from Paleontological collection of the National Museum - Flora. 32450 records from Naturalis National Natural History Museum (NL) – Invertebrate specimens from marine expeditions. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 97 records from LauWi. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 114 records from BIRDRACE VIE will rock you!. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 1968 records from (Appendix B) Distribution of planktonic foraminifera at DSDP Hole 72-518. 30 records from Benthic foraminifera abundance of Hole 42-379A. 102 records from Range table from planktonic foraminifers in ODP Hole 169-1035D. 1 records from Results of palynological analysis of Hole 302-M0004C. 30 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 1092 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 22625 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 2120907 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 6186 records from Chinese mitten crab (Eriocheir sinensis) occurrences in Flanders. 48 records from Wahner Heide LK 12 Biologie. 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 10183 records from Planktic foraminifera counts of sediment core MD95-2040. 135 records from Total foraminifera counts of multinet M11/1_MSN522. 133 records from Total foraminifera counts of multinet PO247/2_MSN1381. 4 records from Counts (3) of calcareous dinocysts along profile Stevns-Klint. 64 records from Feuchtbiotop Weidenkaule. 1726 records from KTU Pinophyta. 21 records from Nannofossil abundance of Hole 24-232A. 18 records from Benthic macrofauna abundance of sediment core 13201-002. 271 records from Planktic foraminifera counts of sediment core RC11-147. 139 records from Corvids Literature Database. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 906 records from Digital Florula - Las Cruces Biological Station. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 92 records from Total foraminifera counts of multinet M26/1_MSN845. 8 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 9 records from Nannofossil abundance of Hole 60-455. 5 records from Distribution of Quinqueloculina sp. in sediment core 13078-017. 30302 records from Arizona State University Amphibian and Reptile Collection. 448 records from Harpactus Shuckard. 30 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-913B. 1 records from Notizen über Oribatei (Acari). III. 47 records from Schulgelände Ceciliengymnasium. 103 records from BIRDRACE Die Otzberger. 135 records from Total foraminifera counts of multinet M21/3_MSN688. 482 records from Total foraminifera counts of multinet M6/7_MSN91. 21 records from Phytoplankton abundance at the sea bottom off Sechura in january 2007, Peru. 1191 records from Relative abundance of Neogene nannofossils at ODP Site 138-850 from the eastern equatorial Pacific. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 32762 records from Fish tag database. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 20 records from Mikroorganismen. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 47 records from Foraminifera species abundances from tow TT007_3-MOC6. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_13-CTD162. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-06-2. 115 records from Nannofossil abundance of Hole 29-279A. 6 records from Benthic macrofauna abundance of sediment core 13077-019. 67 records from (Table 5) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 2019 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 1306 records from Flora genérica de las gramíneas del estado de Tlaxcala. 7076556 records from Great Backyard Bird Count. 5 records from Analyses of the recent components of sediment core PS1400-4. 48 records from Freiheitsring (Frechen). 67 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 1142 records from Range table from planktonic foraminifers in ODP Hole 154-925A. 836970 records from Bernice P. Bishop Museum. 2775 records from (Table T4) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1050C. 49 records from Additional records for Stenosagola newtoni Park & Carlton, 2013 (Staphylinidae: Pselaphinae: Faronitae), with notes on aedeagal morphology. 2265 records from Algae, Specimens, Agder naturmuseum (KMN). 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 315 records from Planktic foraminifera counts of sediment core RC17-69. 569 records from (Appendix A) Planktonic foraminiferal abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-9. 2 records from Kirchenforst. 30 records from Nannofossil abundance of Hole 8-71. 22 records from Nannofossil abundance of Hole 9-83A. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 1496 records from (Table 4) Distribution of planktonic foraminifers in ODP Hole 108-658A. 2070 records from (Table 4) Plio-Pleistocene benthic foraminifera of ODP Hole 107-652A. 3023 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 18274 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 4303 records from Odonata Collection. 84521 records from BioGIS - Vascular plants - INPA database. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 6 records from Phytoplankton abundance at station Rigel_1_2005-03 in March 2005, Chipana, Chile. 130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4. 31 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part III. 1551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 1541 records from (Appendix B3) Calcareous nannofossils of ODP Site 208-1263. 51 records from (Table 8) Percent distribution of calcareous nannofossils at ODP Hole 125-781A. 12 records from Ficha de Sonora aemula. 3761 records from Mountain Invasion Research Network (MIREN) survey. 61234 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 11708 records from The Erysiphales Collection at the Botanische Staatssammlung München. 131 records from Unser Schulhof - eine Apotheke. 34 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 241 records from Planktic foraminifera abundance of Hole 67-499B. 1741 records from Benthic foraminifera abundance of Hole 84-570, Part 1. 73 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 13 records from Collection Reptilia fossil SMF. 9 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (2000m section). 57 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Tityridae. 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 851 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 56302 records from Kathryn Kalmbach Herbarium. 160 records from Wirbach-Taubental (Bad Blankenburg). 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 6 records from Nannofossil abundance of Hole 7-63. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/107-5. 57 records from Nannofossil abundance in sediment core PS1311-4. 49 records from Abundance of calcareous nannofossils across the K/T boundary at ODP Hole 113-690C (Table 1). 998 records from Korean Ethnobotany Database. 5159 records from CNHE/Coleccion Nacional de Helmintos. 195264 records from U.S.D.A. Forest Service, Redwood Sciences Laboratory - Lamna Point Count. 22 records from Sediment properties of core PLG95B_06BOXG. 342 records from (Table A.10) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (150-500 µm). 2128 records from Universitat de València, Colecciones de Criptógamas: VAL_Algae. 90 records from Schulhof Bühlschule Giengen. 2945 records from (Figure 4) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Site 71-512. 54 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 2324 records from Eriophyoid Mites of Poland. 3941 records from UAFMC Mammals. 1069 records from ZFMK Sound Archive. 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 5733 records from Small Mammal Research Database. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 372 records from Colección de Entomología - Arthropoda. 69797 records from Lepidoptera collection, Natural History Museum, University of Oslo. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 98423 records from Insect species recorded in sugarcane fields of Khon Kaen Province, Thailand, over three seasons in 2012. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 6 records from Sediment properties of core PLG93_BCORE1. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 170 records from Scottish Natural Heritage - The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_5-CTD56. 2268 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-173-3. 70 records from Parkuntersuchung Weißer See. 94 records from Coccolith counts of multinet SO119_MSN1298. 19 records from Nannofossil abundance of Hole 31-298. 44 records from (Table 6) Distribution of nannofossils in DSDP Hole 87-583G. 76 records from Coccoliths in sediment core PS1533-3. 9 records from (Table 2) Macrobenthos on the floor of the West Bay of the Furugelm Island, Sea of Japan. 1028827 records from SEAMAP - marine mammals, birds and turtles. 5512 records from Vascular Plants Collection of National Museum of Nature and Science. 93 records from CCUG Microorganisms databases(Fungi). 54059 records from Pelagic Fish Observations 1968-1999. 154 records from Planktic foraminifera distribution of sediment core TRI171-27. 97 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 4051 records from Homoptera. 862 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 1853 records from Yeast Collection in BCRC. 1145 records from Colección de Anélidos. 1 records from Nothrus biverrucatus. 43066 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 323 records from CNAN/Pseudoscorpiones. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 43 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV30_1. 17980 records from Impetus - Herbarium Hamburgense. 302 records from Stadtpark Sulzbach-Rosenberg. 8858 records from (Appendix 2a) Foraminiferal analyses of research borehole Sonder Vium. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 40 records from Stable carbon and oxygen isotope ratios of calcareous dinoflagellate cysts and planktic foraminifera from the Campanian/Maastrichtian section of ODP Hole 113-690C in the Weddell Sea (Table 1). 320 records from Myxomycetes collection of the University of Eastern Finland. 886 records from Lepidoptera Observations from New Zealand by Donald Hobern. 265 records from CNIN/Mantodea. 365 records from Bird Specimens of Miyazaki Prefecture Museum of Nature and History. 353 records from Planktic foraminifera distribution of sediment core GIK17940-2. 40 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D4. 107 records from Planktic foraminifera abundance of Hole 18-180. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 47 records from Université Pédagogique Nationale de Kinshasa (UPN) - Plantes fourragères de la République démocratique du Congo - Projet CABIN. 109176 records from Herps Specimens. 46400 records from Museu Paraense Emilio Goeldi - Ophidia Collection. 168 records from Weidenhüttendorf an der Würm (München). 2 records from Occurrence of mammalia relicts at site Dechenhöhle. 1 records from Planktic foraminifera abundance of Hole 54-420A. 1731 records from (Figure 3) Range of selected planktonic foraminifera in Paleocene samples of DSDP Hole 93-605. 184156 records from The Flora of County Waterford. 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 1 records from Zetes cespitum. 107 records from BIRDRACE Herford Birders. 11 records from A new species of the catfish genus Akysis (Siluriformes: Akysidae) from southern Borneo.. 1 records from Hausgarten. 22908 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 86 records from Fliegenhaupt Marksuhl. 14 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-115BX. 766 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Peces. 25471 records from Ibaraki Nature Museum, Arthropoda collection. 30985 records from MEXU/Asteraceae. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1217-1. 12 records from Abundance of microplankton from bottle APRIL-2000-K2. 81 records from Range table from benthic foraminifers in ODP Hole 172-1061C. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 584 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust Shoresearch. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 311 records from Avena wild species VIR Herbarium. N.I.Vavilov Institute of Plant Genetic Resources (VIR). 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 588 records from Relative abundance of ostracods in sediment core Lz1120. 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 235 records from Total foraminifera counts from multinet M31/3_MSN905. 59 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/424-22. 127 records from Distribution of planktonic foraminifera of sediment core SH1972_2. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 14 records from Benthic macrofauna abundance of sediment core 12930-093. 1130 records from Ostracoda in sediment core PS51/154-11. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 354 records from Relative abundance of planktonic foraminifera in sediment core L-66. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 6 records from Nannofossil abundance of Hole 55-430B. 306 records from (Table DR1) Biofacies, percentages of important benthic foraminifera and isotope data at ODP Site 758. 165 records from (Table 3) Ostracode distribution in ODP Hole 122-761C. 4554 records from Planktic foraminifera counts (census) of sediment core MD96-2080. 88 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 99 records from Planktic foraminifera abundance of Hole 94-610E. 878 records from Planktic foraminifera abundance of Hole 84-568. 32 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 72636 records from Insect Collection of Taiwan Forestry Research Institute. 1322 records from Targeting a portion of central European spider diversity for permanent preservation. 4 records from The Afrotropical Miomantis caffra Saussure 1871 and M. paykullii Stal 1871: first records of alien mantid species in Portugal and Europe, with an updated checklist of Mantodea in Portugal (Insecta: Mantodea). 39 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 190 records from ENBI-Dataset of GART-GloBIS. 356 records from Morphologische Daten von Puffinus creatopus. 17015 records from Cicadelidos (Hemiptera: Cicadellidae) de Colección Entomológica del Instituto Alexander von Humboldt. 86556 records from NINA Vanndata øvrige arter. 20 records from Motzener Tonsee. 161 records from BIRDRACE Nord-Seh-Team. 517 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 141 records from Fig. 7. Relative abundance of ostracod species in composite core JH05. 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 441 records from Pollen analysis of surface samples from Germany and Austria. 1618 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 1393 records from Rancho Grande. 176 records from INSECT COLLECTION. 93 records from Südwestlich der Parkwiesen. 252 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 2 records from Benthic foraminifera abundance of Hole 42-376. 1 records from Pollen and spore abundance of Hole 42-379A. 254 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 2000 records from (Table A2) Sea surface temperature reconstruction of DSDP Site 94-607 in the North Atlantic. 210 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction > 20µm. 3483 records from Irish National Frog Database. 2839 records from Rocky Shore Macroalgae. 70 records from Tab. A6: Anzahl von M. balthica während der Ansiedlungszeit. 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 256 records from BIRDRACE Upupa epöpse. 34 records from Marine Conservation Society - Palinurus elephas or Crawfish sightings in the UK and Ireland from 1969 to the present time.. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 145 records from privater Garten. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 1312 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 30 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/042-2. 3512 records from (Table 3) Plio-Pleistocene benthic foraminifera of ODP Hole 107-653A. 1729 records from Biodiversidad de Datura (Solanaceae) en México. 9728 records from Birds of Ireland. 1271 records from Distribution of planktonic foraminifera of sediment core Core190. 107 records from 1st Austrian Birdrace (Wien). 92 records from Range table from planktonic foraminifers in ODP Hole 167-1017B. 13646 records from Senckenberg - CeDAMar Resource. 90 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 53985 records from BioMar - LIFE project. 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 354 records from Microfossil abundance of Hole 35-323. 524 records from (Table 2) Benthic foraminiferal composition at University of Texas Marine Science Institute (UTMSI) piston cores at Costa Rican slope sediments. 3 records from Antarctic Arrow worms. 24 records from (Table 7) Distribution of Pleistocene to Miocene nannofossils in ODP Hole 108-661A. 27 records from (Table 12) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-666A. 350 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 2723 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 7966 records from MfN - Phasmid Collection. 5 records from Memorial University Botanical Garden Collection. 679 records from Results of palynological analysis of Hole 302-M0004A. 2306 records from (Table T4, T5, T6, T7) Percentage of agglutinated and calcareous benthic foraminiferal species in ODP Hole 178-1098C. 7938 records from Hymenoptera collection, Natural History Museum, University of Oslo. 3 records from Mammalia (SMNH-MM). 7427 records from Weevils of the Tatra Mts.. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 5 records from Streuobstwiese (Mittelgasse 4). 153 records from Selztal bei Friesenheim. 214 records from Binsenwiesen. 57 records from Garten in Schmölln. 18 records from Landschaftsschutzgebiet Buchhorst2. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 347 records from (Table 4) Standing stock values of important species in surface sediments. 49 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 243 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B. 924 records from Antarctic Fur Seal Populations on Heard Island Summer 1987-1988. 9633 records from Coleção Entomológica do Depto. de Sistemática e Ecologia. 320 records from Planktic foraminifera assemblage in sediment core GIK11944-1. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-120BX. 279 records from Planktic foraminifera abundance of Hole 11-98. 2402 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 91 records from Benthic foraminifera abundance of Hole 84-569A. 44 records from Flora und Fauna in unserer Kita. 19555 records from Collection Thysanoptera SMF. 6394 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 29 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 1 records from Celaeno spinosa. 87 records from Klütwald. 36 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12594-2. 102 records from Plasm bearing foraminifera counts of multinet M12/3_MSN559. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 11 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru. 12 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-131BX. 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 1 records from Nothrus echinatus. 2268 records from (Table 1) Distribution of Cretaceous-Tertiary benthic foraminifers in ODP Hole 129-802A. 68 records from Range table from benthic foraminifers in ODP Hole 144-873B. 54 records from Outer Hebrides Biological Recording Project - OHBRP Vertebrates (except birds and restricted records) Dataset - Outer Hebrides. 2079 records from (Table 1) Occurrence and frequency of benthic foraminifera in Paleocene samples of DSDP Hole 93-605. 139 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 49637 records from Monitoring data from the federal state Hesse (Germany). 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 181 records from Total foraminifera counts from multinet M31/3_MSN914. 122 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1359. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 102 records from Foraminifera species abundances from tow TT011_11-MOC72. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-15-3. 5 records from Distribution of meiobenthos in sediment core M19_201-2 of the northeastern Atlantic (Table 1). 820552 records from Fauna Atlas N.T.. 27 records from Zwickau- Schwanenteich. 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 20973 records from Real Jardin Botanico, Madrid: MA-Funhist. 154124 records from Arizona State University Lichen Collection. 718 records from Zukünftiges NSG Höftland/Bockholmwik. 1 records from Planktic foraminifera abundance of Hole 8-73. 9371 records from Range table from planktonic foraminifers in ODP Hole 152-918D. 494248 records from British Lichen Society - BLS Mapping Scheme dataset, 1750-2009. 12768 records from (Table 4) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-872C. 764 records from BioGIS - Fish - INPA database. 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Laguna Las Barrancas (Spitznagel, octubre 1999). 6422 records from Ájtte. 36613 records from Inventaire National du Patrimoine Naturel : Amphibiens et Reptiles de France (Enquête 1). 233 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 47499 records from Sphaeroceridae Collection. 133656 records from NINA insect database. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 144765 records from Invertebrates Collection of the Swedish Museum of Natural History. 44 records from Total foraminifera counts of multinet M21/4_MSN721. 16 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 2916 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 2970 records from (Table 2) Distribution of planktonic foraminifera in the latest Oligocene to Holocene section of ODP Hole 149-897C. 96 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 57 records from Occurrence of mammalia relicts at site Moladova V. 1 records from Range table from planktonic foraminifers in ODP Hole 174-1072A. 246 records from Benthic foraminifera abundance of Hole 73-524. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 11268 records from Aphidoidea Collection. 1 records from Damaeus auritus. 5042 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of Environment. 365 records from Colección Herpetológica de la Patagonia. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 8 records from Krittenhorster Wald (Ostkilver). 114 records from BIRDRACE Di-Bi-Di-Birder. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 144 records from Planktic foraminifera of surface sediments off Portugal and Morocco (Table 4). 1 records from Microzooplankton abundance and biomass at station TT054_24-22. 18026 records from Herbario micológico de La Universidad de La Laguna, Tenerife: TFC_Mic. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 15 records from Diatom abundance measured on water bottle samples at station PS58/009-2. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 921 records from Planktic foraminifera counts of sediment core RC14-37. 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 578 records from (Figure 2c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3239. 33 records from Astyanax endy (Characiformes: Characidae), a new fish species from the upper Río Bermejo basin, northwestern Argentina.. 87053 records from Mycology herbarium, Oslo (O). 5 records from Aretidris, a new genus of ants (Hymenoptera: Formicidae: Myrmicinae) from the mountains of Luzon Island, Philippines. 767 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 193 records from Total foraminifera counts of multinet M21/3_MSN663. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 74 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core GIK23059-2. 2 records from Microzooplankton abundance and biomass at station TT050_19-3. 3 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 30008 records from Lepidoptera specimen database of Japan. 129 records from Benthic macrofauna abundance of subcores of sediment core 12930-084. 1295 records from Planktic foraminifera counts of sediment core RC08-49. 3982 records from Plant (GFEI-PL). 27828 records from svalbardflora.net. 262 records from (Appendix 6) Stable oxygen isotope record of Globigerina bulloides and abundance of Neogloboquadrina pachyderma in sediment core MD95-2041. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 30 records from Leben auf einer Sturmfläche. 92 records from Plasm bearing foraminifera counts of multinet M26/1_MSN843. 316 records from Planktic foraminifera counts of sediment core V14-101. 21350 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 1 records from Flora of Suriname, volume VI, part I. 50 records from Plasm bearing foraminifera counts from M35/1_MSN1047. 276 records from Planktic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 145 records from Phytoplankton abundance at station CD46_0405C#7. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 127 records from Collection Hydrozoa - ZMB. 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 1154 records from Collection Plecoptera - SMF. 1626 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1119. 73043 records from North Carolina State Museum of Natural Sciences Fishes Collection. 212 records from (Table T4) Planktonic foraminifera abundance of ODP Site 170-1042 sediments. 1387 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 82 records from Countryside Council for Wales - Non-native species records from Countryside Council for Wales (CCW) non-native monitoring research and ad-hoc sightings. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 83 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 2 records from Nannofossil abundance of Hole 6-49. 9 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-7. 55 records from (Table 2c) Species compositioon of planktonic foraminiferas in bottom sediments from Core ML1_66. 407 records from Myriapoda - SMF. 9187 records from (Table 14) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-714B. 1023 records from Spencer Entomological Museum. 141 records from Schulhof und Anlagensee in Nellingen. 269 records from 3. Tag der Artenvielfalt Hockenheim. 20 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 76 records from Occurrence of mammalia relicts at site Vindija. 53 records from Occurrence of mammalia relicts at site Roter Berg bei Saalfeld. 6 records from Planktic foraminifera abundance of Hole 23-226. 177 records from (Table 11) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-589. 55 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2008. 159 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 599 records from NHT flora. 81051 records from UPCB - Herbário do Departamento de Botânica. 10567 records from Coleoptera collection of National Museum of Nature and Science. 2 records from Parvimyrma gen. nov. belonging to the Solenopsis genus group Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 22 records from Colección Parasitológica del Centro Nacional Patagónico (CNP-PAR). 88 records from Birdrace_Die_Polyglotten-Saarlouis. 1530 records from (Appendix B) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747C. 314 records from (Appendix 1a) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber in the Holocene section of sediment core GeoTu_SL096. 86 records from Pollen analysis of sediment core GIK16856-2. 39 records from Mineralogy of serpentine muds of ODP Leg 125 holes (Table 1). 193 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-86. 189 records from (Table A.09) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (125-250 µm). 2148 records from Eppingen und Umgebung. 2346 records from (Fig. 8) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 44-391C in the North Atlantic. 1139 records from Phytoplankton abundance in surface water in September 1996, Ilo, Peru. 631 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 11 records from Observation of birds at station PS14/156 along 49° West. 677 records from Meiofauna abundance of central Mediterranean Sea mud volcano sediments. 39401 records from MSB Bird Collection (Arctos). 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 11340 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 29002 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. Coleóptera. 17 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 313162 records from Observational database of Icelandic plants. 11300 records from Eastern Canada Benthic Macro Fauna (OBIS Canada). 2483 records from Bacteria collection of National Institute of Public Health, Poland. 9031 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 296 records from DJH. 127 records from Range table from planktonic foraminifers in ODP Hole 171-1053B. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1100C. 456 records from Range table from benthic foraminifers in ODP Hole 144-873A. 43 records from Bryconops magoi and Bryconops collettei (Characiformes: Characidae), two new freshwater fish species from Venezuela, with comments on B. caudomaculatus (Gunther).. 5336267 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Pelops phaeonotus. 1 records from Diatom abundance of Hole 95-613. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 767 records from BioGIS - Bats - Asaf Tsoar database. 81329 records from natagora-earlybirds. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 163 records from Tiere und Pflanzen am Pfannenbach. 87 records from Total foraminifera counts of trap L2_92_B49. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 4 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1). 34 records from Urolophus kapalensis sp. nov., a new stingaree (Myliobatiformes: Urolophidae) off eastern Australia.. 4 records from Nannofossil abundance of Hole 29-281A. 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 1269 records from Distribution of benthic foraminifers (living) in surface sediments (Table 4). 1042 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 26193 records from Marie-Victorin Herbarium (MT) - Bryophytes. 4024 records from Sightings Map of Invasive Plants in Portugal. 3621 records from Millenium Seedbank (MSB). 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 244 records from WildesMoor bei Schwabstedt. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 82 records from Foraminifera species abundances from tow TT011_5-MOC63. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 13865 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 1664 records from Zooplankton of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 100733 records from South African Institute for Aquatic Biodiversity - Fish Collection (AfrOBIS). 3 records from Analyses of the recent components of sediment core PS1215-2. 668 records from Naturschutzgebiet Sistig-Krekeler-Heide. 973 records from Range table from planktonic foraminifers in ODP Hole 157-954B. 3 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 905 records from Collection Graptolithina fossil SMF. 7 records from Additions to the myxobiota of the Åland Islands. 4 records from Arthropoden aus südostalpinen Höhlen.. 99 records from Düne am Ulvenberg (Darmstadt). 147 records from Total foraminifera counts of multinet M36/6_MSN1195. 16 records from Dinoflagellate cysts of surface sediments. 1 records from Microplankton counts and carbon biomass at station TT007_15-CTD160. 26 records from Ostracoda abundance of Hole 13-132. 88 records from Catalogue of type specimens of fungi and lichens deposited in the Herbarium of the University of Granada (Spain). 104 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Murcielagos. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 73 records from Planktic foraminifera abundance of Hole 2-11. 692 records from Planktic foraminifera abundance of Hole 40-360. 2034 records from Herbarium of Namur. 94 records from Planktic foraminifera abundance of Hole 80-550. 15 records from Range table from planktonic foraminifers in ODP Hole 169-1036A. 1512 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 1 records from The Oribatid Family Phthiracaridae I. Introduction and Redescription of Hoplophthiracarus pavidus (Berlese). 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 25128 records from rmca-albertine-rift-butterflies. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 144 records from Total foraminifera counts of multinet M21/2_MSN640. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 18 records from (Table 1) Early Miocene and late Oligocene ostracods in sediment core CRP-2A. 60000 records from Birds (NSMK-BI). 25371 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 16 records from Nannofossil abundance of Hole 47-398B. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 1379 records from Organic-walled dinoflagellate cyst counts of sediment core GeoB9503-5. 143 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 105 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 8 records from Occurrence of mammalia relicts at site Grotte du Prince. 6264 records from (Table 2) Planktic foraminiferal abundance in Eocene to Oligocene sediments of ODP Hole 177-1090B on the Agulhas Ridge, South Atlantic. 1051 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 569 records from (Appendix D) Benthic foraminifera extinction group species in DSDP Hole 94-608. 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 311768 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 464 records from Lepidoptera collection, NTNU, Trondheim. 84 records from BIRDRACE Vogelscheuchen. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 90 records from Total foraminifera counts of multinet PO231/3_MSN1332. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 4 records from Microzooplankton abundance and biomass at station TT054_24-21. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-097BX. 161 records from (Table 3) Palynomorph concentrations for ODP Site 105-645. 988 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 190 records from Colección Paleontológica Invertebrados e Icnologia - CONICET- Argentina. 91 records from CNIN/Tipos Homoptera. 31 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 143763 records from University of British Columbia Herbarium (UBC) - Algae Collection. 940 records from Benthic foraminifera abundance of Hole 84-570, Part 2. 227 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 27264 records from Formidabel; Belgian Ants Database. 75 records from (Table S2b) Nannofossil species richness in the Wilson Lake section. 1030627 records from Phanerogamic Botanical Collections (S). 28702 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 810 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 216778 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 72 records from Plasm bearing foraminifera counts of multinet M21/1_MSN603. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 7950 records from European riparian ground beetles. 28 records from (Table 1) Mineralogy and abundance of Truncorotalia tosaensis in ODP Hole 194-1195A. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 56051 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 44501 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 1346 records from Percentages of planktonic foraminifera species in sediment core V25-59. 65 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 260 records from Range table from planktonic foraminifers in ODP Hole 155-930D. 92 records from Siliceous microfossil occurrence, Site 177-1094. 55 records from Three new species of Ametadoria Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, Costa Rica. 45 records from Parcela Permanente en el Pantano Martos. 264743 records from ArtenFinder. 187 records from Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae).. 1863 records from Cowan Tetrapod Collection - Herpetology. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 364100 records from University of Florida Vertebrate Paleontology. 9948 records from Bees of Canada / Gschwendtner property collection. 2 records from New distribution records for the rare genus Afrotremex Pasteels (Siricidae: Hymenoptera) and provision of interactive Lucid identification keys to species. 160 records from Total foraminifera counts of multinet M21/2_MSN658. 753 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_5-CTD51. 6 records from Microzooplankton abundance and biomass at station NBP97-08-04-5. 2 records from Smear slide analysis of sediment core GeoB7427-2. 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 1432 records from Quaternary benthic foraminifera abundance of Hole 95-612. 226 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 610 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_107MC. 281250 records from Quadrige. 237 records from RSPB - Capercaillie national surveys (SCARABBS). 1078 records from Fishes of the Congo River 2010 Expedition. 609 records from Countryside Council for Wales - Bat Roosts Database- South Wales. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 54 records from Wiese am Unterbecken. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 33 records from Foraminifera species abundances from tow TT007_2-MOC4. 706 records from (Table 1) Benthic foraminifera at DSDP Site 72-516. 42619 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 66 records from Range table from ostracoda in ODP Hole 151-910D. 29 records from Composition of the fine silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE258. 15016 records from iziko South African Museum - Fish Collection (AfrOBIS). 34506 records from Herbarium de Geo. B. Hinton, México. 302 records from Range table from benthic foraminifers in ODP Hole 144-874B. 195 records from Phytoplankton abundance in surface water in May 1997, Callao, Peru. 2117 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 1 records from Nouvelles fourmis de l'Imerina oriental (Moramanga etc.).. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 23 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2. 6 records from Ökosysteme rund um Wedel. 104 records from Ross Sea Pycnogonids. 102 records from Ostracod abundance in sediment core Lz1120. 155 records from Bergbaufolgelandschaft am Muldestausee. 994 records from (Table 6) Quaternary planktonic foraminifers at DSDP Site 65-483. 465 records from Range table from planktonic foraminifers in ODP Hole 159-959A. 535 records from Benthic foraminifera abundance of Hole 73-522. 31 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 1627 records from The Irish Squirrel Survey 2007. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 19451 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 2877 records from Flea collection of Slovenian Museum of Natural History (Slovenia only). 17 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/011-3. 777 records from Planktic foraminifera counts of sediment core RC17-108. 148 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE293. 5 records from Phytoplankton abundance at station Rigel_5_2005-07 in July 2005, Chipana, Chile. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 12 records from Distribution of meiobenthos in sediment core M23_134 of the northeastern Atlantic (Table 1). 8 records from Abundance of radiolaria at station LV28-29-1. 36845 records from MfN - Fossil invertebrates Ia. 2 records from Nannofossil abundance of Hole 74-526. 461 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 26375 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 535 records from Percentages of planktonic foraminifera species in sediment core V30-41. 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 342 records from Distribution of planktonic foraminifera in sediment core R657 east of New zealand. 131 records from Artenvielfalt auf dem Schulgelände. 8 records from Occurrence of mammalia relicts at site Wretton. 741 records from Planktic foraminifera abundance of Hole 20-200. 3651 records from Planktic foraminifera abundance of Hole 72-516F. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 727 records from Range table from benthic foraminifers in ODP Hole 161-975B. 71 records from Range table from nannofossils in ODP Hole 199-1215A. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 14 records from Collection Pantopoda SMF. 3034 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 1990 records from Seabird 2000. 1 records from Emesopsis infenestra Tatarnic, Wall & Cassis, 2011 (Heteroptera: Reduviidae), genus and species new to New Zealand. 23146 records from BC Coastal Waterbird Survey. 855 records from (Table T7) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones Palpha-P3b. 588 records from Distribution ashore and breeding places of southern elephant seals (OBIS South America, SOUTHERN OCEAN SUB-NODE). 577 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 106 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Dana Uster. 366 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 3015 records from Bird specimens in Gifu Prefectural Museum. 124 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 93712 records from Herbarium of Umeå University (UME). 2050 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 27 records from Benthic foraminifera abundance of Hole 34-320A. 75 records from Range table from nannofossils in ODP Hole 199-1220A. 585 records from (Tab. 4) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 11-105, Bahama Lower Continental Rise Hills. 1474 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 404 records from Greater Manchester Ecology Unit - Water Vole Distribution for Greater Manchester. 3082 records from dec2011. 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 9123 records from Flora of Słowiński National Park, Poland. 527 records from Inventaire floristique de Beza Mahafaly. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 13968 records from NYSM Birds. 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 112 records from BIRDRACE Gütersloher Gimpel. 67 records from Tongrube bei Hettstedt. 57 records from Schulgarten Janusz-Korczak-Realschule. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_1-CTD8. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 45 records from Wasser-Lernort Nettemündung. 1000 records from Plant (KOBG_PL). 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 15 records from Herdengelhoehle taxa and datings. 44 records from Planktic foraminifera abundance of Hole 19-188. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 1 records from On the Chilopoda from Turkey. 2925 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 11729 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 4605 records from CHAS Mammalogy. 69622 records from Fundación Miguel Lillo - Colección Entomológica. 96 records from Birdrace-federleser-Herford. 100 records from Birdrace-The_Ringers-Friesland. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 20991 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 5037 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 1 records from Antarctic Marine Amoebae. 156 records from (4) Assemblages of planktic foraminifera and Sea Surface Temperature (SST) reconstructed from the Modern Analogue Technique in sediment core MD02-2488 during the Last Interglacial. 73544 records from Marsh Monitoring Program - Birds. 1833 records from DSMZ Fungi. 13702 records from Fundación Miguel Lillo - Colección Ornitológica. 7032 records from EAN - Herbário Jaime Coelho de Moraes. 3535 records from Colección de Entomología Médica del Instituto Colombiano de Medicina Tropical. 112 records from Total foraminifera counts of multinet M11/1_MSN526. 51 records from Total foraminifera counts of multinet M21/4_MSN712. 1 records from Nothrus scaliger. 40 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2215-1. 11431 records from Herp Specimens. 1634 records from ZFMK DORSA. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/091-4. 349 records from Planktic foraminifera counts of sediment core V20-170. 2050 records from Birds (ENHM-BI). 149 records from A multi-proxy investigation of sediment core GeoB7165-1 ~60 km offshore Concepción. 471 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part III. 438 records from (Table 4) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-709A. 5429 records from Ibaraki Nature Museum, Algae collection. 4100 records from Actualización de la base de datos de crustáceos de la Colección Biológica de la Secretaría de Marina. 11054 records from Colección de Sifonápteros del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 340 records from Occurrence of mammalia relicts at site Brillenhöhle. 24 records from Occurrence of mammalia relicts at site Overmere. 7 records from Radiolaria assemblage in sediment core GIK23424-3. 520 records from Planktic foraminifera abundance of Hole 39-357. 2083 records from Planktic foraminifera abundance of Hole 72-517. 115 records from Range table from planktonic foraminifers in ODP Hole 155-931C. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 7 records from Range table from planktonic foraminifers in ODP Hole 192-1185B. 102 records from Benthic foraminifera abundance of Hole 42-372. 157 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 1 records from Microfossil abundance of Hole 42-378. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 1 records from Abundance of benthos infauna at station GIK23062-2. 57 records from Heidesee / Halle. 147 records from NABU-Auerochsenweide. 50 records from Plasm bearing foraminifera counts of multinet SO118_MSN1267. 77 records from Total foraminifera counts of multinet PO231/3_MSN1330. 8 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_11-CTD137. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 212 records from Nanoplankton abundance at station GeoB2017-1. 1356 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 52 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 19 records from Dinoflagellate abundance of Hole 81-553A. 1312 records from (Table 3) Distribution of benthic foraminifers in the > 63 µm fraction in surface sediments from the central Arctic Ocean. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 681 records from (Appendix) Planktonic foraminiferal abundances in ODP Hole 130-805C. 2387 records from The French Collection of Medicago truncatula. 1 records from Porifera ZMK. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 46 records from Foraminifera species abundances from tow TT007_5-MOC9. 180 records from Range table from ostracoda in ODP Hole 144-871A. 845 records from Estudio comparativo del zooplancton en dos regiones de México. 28934 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 495 records from Field Study Group of the Dutch Mammal Society (NL) - 2013 - Mammal Survey Western Rhodopes, Bulgaria. 25 records from A new Gymnotus (Teleostei: Gymnotiformes: Gymnotidae) from the Pantanal Matogrossense of Brazil and adjacent drainages: continued documentation of a cryptic fauna.. 3 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 228 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 14473 records from Entomology at ZMUC, Natural History Musem of Denmark. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 1537 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 108-657A. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 777 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 8684 records from Individual Sightings. 2241402 records from Biologiezentrum Linz. 1843 records from (Table 3) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583. 944 records from Range table from planktonic foraminifers in ODP Hole 192-1183A. 498 records from Dinoflagellate abundance of Hole 94-611C. 736 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 156 records from Colecciones Zoológicas de la Universidad de León, Colección de Malacostráceos. 139 records from Siliceous microfossil occurrence, Site 177-1093. 14532 records from MVZ Egg and Nest Collection (Arctos). 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 5262 records from Spider Mites Collection of Jean Gutierrez. 21 records from Unveiling of a cryptic Dicranomyia (Idiopyga) from northern Finland using integrative approach (Diptera, Limoniidae). 1968 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Pinus sylvestris pioneer forest. 3025 records from SMNS Palaeontological collection - Fossil amphibes and terrestrian reptiles. 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 116 records from (Table 17) Distribution of planktonic foraminifers in ODP Hole 108-668B. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 355 records from (Table A3) Semi-quantitative frequency of Globorotalia menardii in core SO164-17-2. 72615 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 70704 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1988) (AfrOBIS). 35693 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2002) (AfrOBIS). 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 94474 records from TNHC Herpetology Collection. 66 records from Visual Plants (144.41.33.158) - Private collection of Thorsten Kroemer. 3224 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 11037 records from The Bat Conservation Trust - Noctule, Serotine and Pipistrelle Field Survey. 294 records from Naturgarten Langenholtensen. 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 42 records from Foraminifera abundance of Hole 24-236. 172 records from Foraminifera abundance of Hole 59-448A. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 960 records from (Table 11) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-591. 72 records from Range table from benthic foraminifers in ODP Hole 198-1213A. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 1087 records from The Bat Conservation Trust - Bechstein's Bat Survey Project. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 13545 records from Collection Bryozoa SMF. 485 records from UAM Herpetology Collection (Arctos). 1 records from Nouvelles fourmis d'Afrique.. 344 records from (Table T13) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones Palpha-P3b. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Formicariidae. 1998 records from Aves de la cuenca media del río Bogotá. 1 records from Nothrus pollinosus. 91 records from BIRDRACE SchrägeVögel. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 163 records from Total foraminifera counts from multinet SO119_MSN1285. 171 records from Total foraminifera counts of multinet M42/3_MSN1370. 35 records from Nannofossil abundance of Hole 78-543. 2000 records from Shellfish (ASJK_MS). 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 424 records from Bulk components and planktonic foraminifera of sediment core GeoB3375-1. 19 records from Microplankton data off Mejillones, 2006, Chile. 36 records from Range table from planktonic foraminifers in ODP Hole 144-877A. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 100 records from Total foraminifera counts of multinet M12/3_MSN536. 222 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 39615 records from Irish vascular plant data 1999-2009. 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 255 records from GENT Lactarius Deliciosi. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 1733 records from Birds collection of Abiko City Museum of Birds. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 76 records from Faunal assemblage of sediment core GS7603-10. 11 records from Content of coarse fraction and G. menardii in sediment corev V25-39. 8 records from Phytoplankton abundance at station Rigel_6_2005-03 in March 2005, Chipana, Chile. 135 records from (Table A.08) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (80-150 µm). 36 records from Nannofossil abundance of Hole 14-141. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/580-2. 596 records from Planktic foraminifera counts of sediment core A15-558. 1409 records from Planktic foraminifera counts of sediment core AB000280. 591 records from Planktic foraminifera counts of sediment core V16-25. 753 records from Planktic foraminifera counts of sediment core V28-127. 484 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 117-726A. 2792 records from Birds (UWEP-BI). 145 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 20 records from (Table 2c) Nannofossil distribution chart of ODP Hole 122-762C. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 169 records from Planktic foraminifera counts at CTD station PS55/051. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1b. 6 records from Nannofossil abundance of Hole 6-49. 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 1134 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 718087 records from Insect (KNAM-IN). 29 records from Description of two new species of Hetereleotris (Gobiidae) from the south Pacific, with a revised key to species and synonymization of the genus Pascua with Hetereleotris.. 1794 records from Herbarium BSG Lichenes. 700941 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Sturnidae. 276 records from Environment Agency - Crayfish data update for Environment Agency Thames Region March 2009. 41857 records from Tasmanian Museum and Art Gallery provider for OZCAM. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 318 records from Geometry of coccolith Coccolithus pelagicus in ODP Hole 104-643A. 129 records from Nannofossil abundance of Hole 29-284. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 1301 records from Collection Hymenoptera SMF. 1088 records from (Appendix 2-1) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 7-62A in the western Pacific Ocean. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 1055 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 9 records from Nannofossil abundance of Hole 1-2. 7 records from Nannofossil abundance of Hole 38-336. 2073 records from Bryophyte collection of Jyväskylä University Museum. 97 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 115 records from (Table 2a) Relative abundance of planktonic foraminiferas in samples of surface sediments and in sediments accumulated about 18 ky ago from typical cores in the area of the Canary upwelling. 168 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2009. 1756 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 7503 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 5205 records from Botanical Garden Collection. 478 records from EASIANET. 16489 records from AIMS - GBR Nearshore Coral Diversity (OBIS Australia). 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 82756 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1992) (AfrOBIS). 2184 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 30501 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 6627 records from ATCC Fungi Collection Catalog. 274 records from Herpetological Collection at the Wildlife Institute of India Vertebrate Museum. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 173 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 98 records from Distribution of palynomorphs in Miocene sediments of ODP Site 188-1165 in the Prydz Bay, East Antarctica (Table 1). 84 records from Benthic foraminifera abundance of Hole 84-566C. 13593 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 7457 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 8455 records from CRI - Herbário Pe. Dr. Raulino Reitz. 200390 records from Mammalogy Collection - Royal Ontario Museum. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 40 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 24121 records from Endemic plants of the Congo basin. 98096 records from CAS Ornithology (ORN). 1 records from Zetes morticinus. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 85 records from Birdrace-Die_Paradiesvögel-Herford. 43 records from Schulgelände Thurmair-Gymnasium. 3 records from Blankenfelder See. 65 records from BIRDRACE Federal Birds of Investigation FBI. 504 records from Schatzinsel Wangerooge. 248 records from Schulgarten der Volksschule. 33 records from Schüler erforschen die Helme-Aue. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 681 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 43 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM5. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 39 records from Red list project inventory, fungi. 303 records from National Botanic Garden Belgium - Martius. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 59493 records from Irish Vascular Plant Data - Paul Green. 17 records from Hazel Dormouse in Ireland. 6 records from Mammalia (JNHM-MM). 95 records from Vielfalt verschiedener Wiesen. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 16087 records from RSPB - Corncrake national surveys - territory centres (SCARABBS). 1301 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-159-1. 16 records from Nannofossil abundance of Hole 9-77B. 8 records from Nannofossil abundance of Hole 49-409. 28 records from (Table 4) Range chart of calcareous nannofossils from Ross Sea sediment cores. 26 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 3726 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 580 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 221 records from (Table 1) Abundance of planktonic foraminifera in ODP Hole 113-689B, large size fraction. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 3468 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 12 records from Nannofossil abundance of Hole 20-200. 260 records from Range table from ostracoda in ODP Hole 144-873B. 2 records from Range table from nannofossils in ODP Hole 198-1207A. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 22 records from Steinbruch Mainz-Weisenau, 4.Jahr. 132 records from Cretaceous ostracods of DSDP Hole 10-95 (Figure 2). 2387 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 2730 records from (Table 10) Distribution of planktonic foraminifera in the middle to late Miocene section of ODP Hole 149-900A. 30000 records from Freshwater Fish Specimens of Lake Biwa Museum. 336 records from Scottish Natural Heritage - Site Condition Monitoring Records from surveys of lamprey species in five river SACs in Scotland. 186 records from Planktic foraminifera abundance of Hole 94-610. 2 records from Range table from planktonic foraminifers in ODP Hole 144-874A. 437 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8063 records from (Appendix B1) Relative abundances of middle Eocene-late Oligocene calcareous nannofossils in ODP Hole 120-748B. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 4042 records from SMNS Palaeontological collection - Tertiary mammals. 4 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 2876 records from Naturalis National Natural History Museum (NL) – Mollusca fossils. 144 records from Endocast Collection -CONICET- Argentina. 945 records from (Table 7) Distribution of planktonic foraminifers in ODP Hole 108-660A. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 495 records from Life Science National Tsing Hua University. 90 records from Collection Ctenophora SMF. 36188 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 655 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 5 records from Nannofossil abundance of Hole 84-569. 7869 records from UWBM Herpetology Collection (Arctos). 14 records from (Table 1) Analyses of coarse fraction of DSDP Hole 94-609. 907 records from Actualización sistemática y electrónica del acervo de gasterópodos de la Colección Malacológica Dr. Antonio García-Cubas (COMA), del Instituto de Ciencias del Mar y Limnología, UNAM. 2299 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 21129 records from Pteridophyta specimens of Shizuoka Prefecture Museum of Natural History. 17374 records from Canadian Museum of Nature Amphibian and Reptile Collection - Anura. 368 records from Great Lakes Forestry Centre Insect Collection. 24 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 19 records from Dinoflagellates, pollen and spore abundance of Hole 29-283. 103 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 15715 records from Herbarium Erlangense. 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 5841 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coleoptera_Types_Orient. 2 records from Nannofossil abundance of Hole 29-280A. 4 records from Akita Prefectural Museum＋Annelids Specimens of Akita Prefectural Museum. 15000 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 8523 records from Distribution of planktic foraminifers of core RC24-16. 994 records from Distribution of planktic foraminifera in sediment core GIK23074-1. 379 records from Relative abundance of planktonic foraminifera in sediment core MK-325. 7 records from Analyses of the recent components of sediment core PS1219-1. 239 records from Naturerlebnisraum Koppelsberg. 15 records from Occurrence of mammalia relicts at site Dendermonde. 1 records from Nothrus theleproctus. 5944 records from (Figure 6) Distribution of benthic foraminifers in middle-upper and Quaternary in DSDP Site 71-512. 1380 records from Range table from benthic foraminifers in ODP Hole 189-1168A. 63646 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 2029 records from National Trust - Sutton Hoo species data held by The National Trust.. 796 records from (Data S1) Palynology of IODP Hole 318-U1356A. 351058 records from Staffordshire Ecological Record - SER Species-based Surveys. 7848 records from Lichen specimen database of Faurie collection. 350 records from Speothos Venaticus por Guillermo Gil. 152 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 27847 records from Dataset of Passerine bird communities in a mediterranean high mountain (Sierra Nevada, Spain). 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 4 records from Nannofossil abundance of Hole 52-418. 1129 records from Mollusca Collection of Saitama Museum of Natural History. 415 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE206. 251 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 1293 records from Base de datos y catálogo de helmintos parásitos de anuros de México. 1 records from Akita Prefectural Museum＋Bryozoans Specimens of Akita Prefectural Museum. 19164 records from The Gordon Alexander Orthoptera Collection. 94 records from Planktic foraminifera abundance of Hole 32-310. 486 records from Corales de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMco). 1 records from Pelops fuligineus. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 233 records from Total foraminifera counts from M35/1_MSN1044. 5 records from A new species of Nanochromis (Teleostei: Cichlidae) from Lake Mai Ndombe, central Congo Basin, Democratic Republic of Congo.. 32 records from Nannofossil abundance of Hole 67-499. 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD35. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 9 records from Coccolith counts of multinet M32/5_MSN982. 3 records from Nannofossil abundance of Hole 22-212. 15 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1095B. 15494 records from (Table 6) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-703A. 1272 records from Registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 325 records from Planktic foraminifera abundance of Hole 32-305. 387 records from Range table from planktonic foraminifers in ODP Hole 182-1134A. 3130 records from Range table from benthic foraminifers in ODP Hole 154-926A. 16 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1024. 2509 records from Type Specimen Database of Museum and Institute of Zoology PAS. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 110 records from Total foraminifera counts of multinet PO247/2_MSN1375. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_2-CTD16. 1796 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 164 records from Planktic foraminifera abundance of Hole 94-610B. 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 22 records from Phytoplankton abundance at station Rigel_6_2005-05 in May 2005, Chipana, Chile. 149 records from Bayerische Donau - Neu Ulm. 238 records from Coccoliths in ODP Hole 104-643A. 410 records from (Appendix 3) Planktonic foraminiferal composition from ODP Site 172-1056. 122 records from Review of the ant genus Aenictus (Hymenoptera: Formicidae) in Australia with notes on A. ceylonicus (Mayr).. 353 records from Stadtgebiet (Dannenberg). 226 records from Range table from benthic foraminifers in ODP Hole 182-1130A. 4888 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 133 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Parulidae. 40 records from Tiere und Pflanzen um uns herum !. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 2080 records from Fish tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1636 records from Biodiversity of Antarctic Zoobenthos (SCAR-MarBIN: Antarctic OBIS). 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 10744 records from RSPB - Bringing Reedbeds to Life Invertebrate Survey of three key reedbed sites in England in 2009, 2010. RSPB led project with 50% funding from Natural Engl. 19984 records from HRCB - Herbário Rioclarense. 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 59 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1388. 22 records from Content of coarse fraction and G. menardii in sediment corev V25-47. 152 records from Abundance of planktic foraminifera at CTD station M39/4_402CTD-55. 11 records from Phytoplankton abundance at station Rigel_4_2005-03 in March 2005, Chipana, Chile. 7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 77 records from Occurrence of recent nannoplankton in sediment core M1_MULT242, Arabian Sea (Fig. 2). 7 records from Nannofossil abundance of Hole 5-33. 7 records from Nannofossil abundance of Hole 9-82A. 15 records from Microfossil abundance of Hole 59-450. 126 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 2610 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 240 records from (Table 2) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-766A. 593 records from Ostracoda in sediment core PS51/159-10. 1 records from Berlese's Primitive Oribatid Mites. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 5 records from Schulwald Regionale Schule Sprendlingen. 14 records from Nannofossil abundance of Hole 8-72A. 82 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-699. 775 records from Insect (GNHM-IN). 2478 records from (Figure 3) Range charts of selected dinoflagellate cysts in ODP Hole 122-762C. 85 records from Fig 14. Pollen profile from sediment core Schmiecher See. 164357 records from The Himalayan Uplands Plant database (HUP Version 1). 41548 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 354 records from Foraminifera distribution of sediment core KS310. 125 records from Artenbestimmung. 462 records from Range table from planktonic foraminifers in ODP Hole 155-942A. 122 records from Relative abundance of benthic foraminifera of sediment core GIK13292-3, East Atlantic off Senegal and Gambia (Table 3). 187800 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 172 records from Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals.. 319 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 92 records from The Ants of Bulgaria. 1180 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Water Vole Records. 149 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 54 records from (Table 3) Distribution of nannofossils in DSDP Hole 87-583A. 71 records from Distribution of benthic abyssal gastropods in the Iberian Deep-Sea Basin (Table 2). 2634 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 900 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 15886 records from Insect Specimen Database of Fukui City Museum of Natural History. 3 records from Planktic foraminifera abundance of Hole 54-424B. 5612 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 3956 records from SMDB - Santa Maria Departamento de Biologia. 3422 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 308 records from Wangerooge. 133 records from Total foraminifera counts of multinet M21/3_MSN676. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 35 records from Ortsrand Zandershagen. 143 records from Akita Prefectural Museum＋Malacostracans Specimens of Akita Prefectural Museum. 675 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1400-4. 12 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR72. 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 77 records from Abundance of dinoflagellates and ciliates at time series station Helgoland Roads, North Sea in 2009. 6987 records from Lyman Entomological Museum. 3 records from Acari fossil - SMNG. 41 records from Altholzparzelle Eilenriede Hannover. 10 records from Range table from planktonic foraminifers in ODP Hole 169-1038A. 135 records from Range table from planktonic foraminifers in ODP Hole 180-1114A. 21 records from Hypostomus rhantos (Siluriformes: Loricariidae), a new species from southern Venezuela.. 287 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 5). 439 records from Antarctic and Subantarctic Asteroid zoogeography (SCAR-MarBIN: Antarctic OBIS). 18 records from Redescription of two species of wobbegongs (Chondrichthyes: Orectolobidae) with elevation of Orectolobus halei Whitley 1940 to species level.. 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 2 records from Benthic hard-bottom communities abundance at Lilliguapy in 2010. 15 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 80 records from BB-Biodiversität b. 5265 records from Lower Albian, Niveau Paquier range chart of nannofossils in SE France. 3 records from Nannofossil abundance of Hole 9-80. 48 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-703. 46 records from Antarctic Isopods. 2074 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Aves. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 56 records from Estetal (Buxtehude). 15 records from Kühnauer Aue und Kühnauer See. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD13. 2 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-10-12. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 12 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 316 records from Planktic foraminifera counts of sediment core RC11-86. 317 records from Planktic foraminifera counts of sediment core RC14-29. 703 records from Planktic foraminifera counts of sediment core V25-59. 2210 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 8775 records from (Table 2) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 7311 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 34253 records from MedOBIS (EurOBIS). 34341 records from Historical hyperbenthos data (1987-2001) from the North Sea and some adjacent areas (EurOBIS). 4244 records from Insect Specimens of Lake Biwa Museum. 16 records from A new fungus-growing ant genus, Mycetagroicus gen. nov. with the description of three new species and comments on the monophyly of the Attini (Hymenoptera: Formicidae).. 1597 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 16 records from Abundance of radiolaria at station LV28-3-3. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 269 records from BIRDRACE Dithmarscher Deichhühner. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 7 records from The interstitial subsoil fauna of the upper beach level at Sarso Beach, Red Sea (Table 2). 1148 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 1004 records from Arctic soft-sediment macrobenthos (EurOBIS). 234 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 2. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 81 records from Foraminifera species abundances from tow TT011_6-MOC65. 6 records from Microzooplankton abundance and biomass at station NBP97-08-19-1. 20 records from Nannofossil abundance of Hole 7-63A. 14 records from Nannofossil abundance of Hole 14-140. 704 records from Planktic foraminifera counts of sediment core V18-207. 8336 records from Birds (GMBO-BI). 296 records from (Appendix 1c) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber from MIS 11 of sediment core GeoTu_SL096. 5 records from A Redescription of Conoppia palmicinctum (Michael, 1880) (Acari, Cryptostigmata). 48 records from Nanoplankton abundance at station GeoB2005-5. 1374 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 18192 records from Plant Specimens of The Shimane Nature Museum of Mt. Sanbe. 29 records from Occurrence of mammalia relicts at site la Grotte du Thai. 97 records from Occurrence of mammalia relicts at site Rejtek 1. 60 records from Planktic foraminifera abundance of Hole 19-192. 240 records from Range table from nannofossils in ODP Hole 199-1219A. 816 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 1 records from Nothrus pulverulentus. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 19127 records from Biological Records Centre - Cerambycidae Dataset. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 23 records from Landwehrbach. 581051 records from Swiss National Butterflies Databank. 892 records from Weevils of Wales and England. 123214 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 60 records from Schafsweide Seniorenhaus Berghof. 12 records from Art´n Vielfalt im Kinderwald. 84 records from Anisopodidae and Thaumaleidae (Diptera: Nematocera) of Ireland. 15 records from Abundance and composition of meiobenthos in surface sediments at Fladen Ground stations in August 1975, North Sea (Table 4). 90 records from Planktic foraminifera counts of sediment core RC13-158. 31 records from Bayerische Donau - Tapfheim. 906 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Fitoplancton. 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 1 records from Occurrence of mammalia relicts at site Ejstrup. 2238 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 7 records from Range table from planktonic foraminifers in ODP Hole 182-1132A. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 230221 records from UA Herbarium. 1 records from H. Sauter's Formosa-Ausbeute: Formicidae (Hym.).. 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 28 records from Stadtpark Prinzengarten (Sigmaringen). 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN897. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 86 records from Plasm bearing foraminifera counts from M35/1_MSN1061. 10 records from Microzooplankton abundance and biomass at station TT043_21-22. 6 records from Microzooplankton abundance and biomass at station NBP97-08-28-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 31 records from Nannofossil abundance of Hole 4-23. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 49 records from (Appendix 1) DSDP Site 94-607A ostracode species census data. 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 692 records from Collection Trilobita SMF. 20043 records from Mollusca collection of National Museum of Nature and Science. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 2654 records from Collection of Hymenoptera. 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 1 records from Nothrus posticus. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 100 records from Grenzturm Hohen Neuendorf. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 122 records from Phytoplankton abundance at station CD46_1005C#4. 185 records from Abundance of coccosphere-units of site GIK23414. 2 records from Nannofossil abundance of Hole 7-64A. 16 records from Lepidurus arcticus survey Northeast Greenland 2013. 1097 records from (App 4) Relative contents of benthic foraminifera species in Holocene sediments from Core BP00-07/05. 1208 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1125. 7 records from Megafauna biomass in surface sediment during cruise PLG95A. 358 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of IODP Hole 318-U1356A. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 1402 records from Free-living marine Nematodes from Puerto Madryn and Pozo sandy beaches (Chubut, Argentina), 2006.. 223320 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 9 records from Diaphoromyrma, a new myrmicine ant genus (Hymenoptera: Formicidae) from North Eastern Brazil. 4689 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 188781 records from Reptiles and Amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 85 records from Sedimentological investigation on core V25-45. 3 records from Sarcodine counts and carbon biomass at station TT011_15-CTD168. 508 records from Guyane_Cacaoyer. 203 records from Planktic foraminifera abundance of Hole 72-515B. 525 records from Benthic foraminifera abundance of Hole 40-360. 6 records from Una nuova specie di Eupolybothrus della fauna di Grecia (Chilopoda, Lithobiomorpha). 47 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 1087 records from SMNS Palaeontological collection - Tertiary and quaternary invertebrates. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 76 records from BIRDRACE Nachtigallen. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 198 records from Total foraminifera counts from M35/1_MSN1047. 149 records from Plasm bearing foraminifera counts from M35/1_MSN1046. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 7 records from Distribution of meiobenthos in sediment core M23_199 (2) of the northeastern Atlantic (Table 1). 483 records from Artenvielfalt im Rhein-Neckar-Raum. 303033 records from Natural History Museum, University of Tartu. 49 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Amphipods. 2863 records from Invertebrates compiled by W.Block. 58 records from Lüner Holz (Lüneburg). 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 2274 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 707 records from Benthic foraminiferal assemblages of Upper Cretaceous sediments from DSDP Hole 74-527 in the Angola Basin, South Atlantic Ocean (Table I, Appendix II). 83 records from Abundance of birds on the channels of Lena Delta in the brood period. 691 records from RSPB - Black grouse national surveys (SCARABBS). 3509 records from Entocyther
Keywords: GBIF; biodiversity; species occurrences